Harnessing electromagnetic induction to power nanobiohybrids for efficient degradation of organic pollutants - Mingqiu Hong; Lei Li; Yulin Guo; Chaohui Yang; Jing Hu; Ruihao Xiao; Jie Ye; Shungui Zhou (Water Research, 2026)

Network-based prioritization of sepsis-associated metabolites and in vivo validation of diosmetin in sepsis-associated acute kidney injury - Mingliang Ye; Yinghui Hong; Xi Li; Lei Huang (Molecular Biology Reports, 2026)

New variant in KITLG shapes the pathogenesis of familial progressive hyper- and hypo-pigmentation - Bodan Wu; Ming He; Tongyun Liu; Wenjing Zhao; Jianhong Ye; Tao Jiang; Congcong Teng; Yaxin Huang; Yangjia Zhang; Jiao Li; Hong Shi; Jie Zhang (Molecular Genetics and Genomics, 2026)

Monoterpenoid bisindole alkaloids with intestinal anti-inflammatory activity from Kopsia hainanensis - Jiamin Wang; Niping Li; Zhuoying Lin; Su Nie; Jiabin Huang; Di Zhang; Yiyi Li; Jian Hong; Wencai Ye; Lei Wang (Phytochemistry, 2026)

Selective mitigation of lizardite slime coatings on chalcopyrite flotation using an organic phosphonate depressant: Performance and mechanism - Guangke Ye; Li Zhang; Hong Zheng; Guofan Zhang (Minerals Engineering, 2026)

The role of continental and oceanic subduction in generating the giant Jiaodong gold province, China: Constraints from mercury isotopes - Hong Wang; Ting-Guang Lan; Yang Xu; Hong-Rui Fan; Huan-Long Hu; Lei Shu; Lang‑Ye Zhao; Xing-Hui Li (Gondwana Research, 2026)

Superior removal of phthalate acid esters from water using a magnetic PIM-1 adsorbent - Ruobing Jia; Shunying Li; Keda Guo; Shiqi Yang; Yingying Zhang; Qiangqiang Xu; Hong Ye; Hehe Li; Shuangyang Li; Shengpeng Shi (Chemical Engineering Journal, 2026)

Burstein–Moss band engineering of amine-functionalised In2S3 for visible-light photocatalytic degradation of PFAS - Xiaoyang Song; Hui Xue; Honglei Li; Jiefeng Liang; Xiaomeng Ji; Qiang Song; Patrick J. Cullen; Ye Hong; Runzeng Liu; Xiaoguang Duan; Qingzhe Zhang; Yongguang Yin; et al. (Water Research, 2026)

2D and 3D urban green space configurations shape airborne microbiome diversity and potential pathogen abundance - Yujia Bai; Mingyu Liao; Peter M. van Bodegom; Laiyi Li; Anyi Hu; Mengran Zhou; Shenghui Cui; Hong Ye (Urban Forestry & Urban Greening, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Corrigendum to “A case study of Lepiota brunneoincarnata poisoning with endoscopic nasobiliary drainage in Shandong, China” [Toxicon 161C (2019) 12-16] - Jian Sun; Hong-Shun Zhang; Hai-Jiao Li; Yi-Zhe Zhang; Qian He; Jun-Jia Lu; Yu Yin; Cheng-Ye Sun (Toxicon, 2026)

Solvothermal upcycling of spent LiFePO4 cathode materials into high-voltage LiMn0.5Fe0.5PO4 via a dual-olivine intermediate - Ye Hong; Fan Wang; Chunjiao Hu; Penghui Tan; Tianhua Shang; Heng Kuang; Lingchao Kong; Jin Li; Qianqian Hu; Jian Ouyang; Zilong Tang; Shuaibo Zeng (Journal of Environmental Chemical Engineering, 2026)

Ionic pair-interpenetrated anti-swelling hydrogel membranes for efficient osmotic energy conversion - Huanlin Yang; Guilong Li; Chunmei Zhang; Ye Kang; Fengyun Liu; Jialing Zhou; Jian Wang; Hong Tan (Journal of Environmental Chemical Engineering, 2026)

Concentration-dependent interfacial reconstruction governs the thermal stability of whey protein microgels-sucrose ester hybrid Pickering emulsions - Xiang Li; Yingxiang Li; Qianyi Ye; Yaoxi Zhang; Sihan Cheng; Yikai Chen; Hong Liu; Tongfei Shi; Jie Xiao (Food Hydrocolloids, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Agricultural allochthonous dissolved organic matter is associated with microbial functional differentiation in methane- and nitrogen-related gene profiles in rural rivers - Yi Zhu; Hong Liu; Yongjiao Yi; Zhengyang Li; Jianfeng Ye (Environmental Research, 2026)

Activity-guided discovery of antibiotic-transforming bacteria from environmental microbiomes using D-amino acid–assisted fluorescence-activated cell sorting - Yi Liu; Kai-Li Wang; Yu-Qi Hong; Ye Yuan; Hua Wang; Yi-Qun Chen; Sheng-Song Yu; Zi-Xuan Lu; Yuan Pan; Ting-Ting Zhu (Environmental Pollution, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

Vascular smooth muscle cell FTO deletion aggravates atherosclerotic plaque instability by promoting VSMC migration through the N6-methyladenosine modification of the COL3A1 mRNA - Zhiliang Yang; Keyong Deng; Jiani Wu; Naqiong Wu; Zhifan Li; Shuang Yang; Mengyi Sun; Dan Liu; Xiaotong Ning; Shufeng Chen; Bin Yang; Jue Ye; et al. (Science China Life Sciences, 2026)

Formulation and biological evaluation of a Perilla frutescens seed oil nanoemulsion: A novel therapeutic agent for alleviating gut-liver axis inflammation - Jia-Yu Ye; Wei Zhang; Mei Qin; Hong-Jie Cui; Jian Li (Research in Veterinary Science, 2026)

Alpha-ketoglutarate alleviates Cadmium-induced ferroptosis in association with enhanced mitochondrial function in testes - Xiaofei Wang; Weiwei Dong; Jing Zhao; Ningjing Chen; Tingting Zheng; Yingying Liu; Qinhua Li; Hong Ye; Huiying Li; Liangqun Xie (Reproductive Toxicology, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Low enthalpy 3D evaporators coupled with auxiliary thermal management for rapid solar evaporation - Ze-Ming Huang; Hong-Yu Chu; Ye-Tong Liu; Xiang-Jing Mo; Jing Li; Chong-Chen Wang; Peng Wang; Xiao-Hong Yi (Chemical Engineering Journal, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

Heavy metal pollution and associated health risk assessment in wild oysters from the Guangdong coast, China - Xiaomin Li; Xin’an Yue; Yaohui Chen; Jianping Ye; Zihua Zhou; Hong Qiu; Hua Wang; Jingxin Liu; Shengyong Li; Jinghuai Zhang (Marine Pollution Bulletin, 2026)

Calculating Receptor Occupancy using TMDD Models – What has to be Considered? - Yu Fu; Liang Yang; Hong Su; Ye Yao; Yu Li; Peiming Ma (The AAPS Journal, 2026)

Exploration of the rare 5/6/7-fused diterpenoids with anti-hypertrophy activity from Strophioblachia glandulosa via bioactivity-guided strategy - Xue-Wen Wu; Hong-Ye Zhang; Yu Qin; Yu-Tong Xing; Bin-Bao Wang; Wei-Lie Xiao; Chang-Bo Zheng; Xiao-Li Li (Phytochemistry, 2026)

Undescribed and nephroprotective diterpenoids from Daphne genkwa - Hong-Bo Ye; Xian-Run Wu; Li Wang; Hui-Zhen Peng; Yu Duan; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2026)

Design and characterization of a novel vehicle-mounted dual-reactor smog chamber for controlled and real-world atmospheric process simulations - Chenghao Liao; Chao Peng; Weiqiang Yang; Chenshuo Ye; Wei Song; Junling Li; Hong Li; Yongbo Zhang; Xinming Wang (Journal of Environmental Sciences, 2026)

Combined bearing capacity of spudcan considering installation effect in clay - Ye Tian; Jiang Tao Yi; Si Yu Li; Hong Yu Tang; Xiao Han; Jing Nian Ran (Computers and Geotechnics, 2026)

Charge-spin-orbit modulated hollow carbon sphere-encapsulated Co9S8/CoS heterojunctions for high-performance sodium-ion batteries - Hao Yang; Dehua Li; Hong Gao; Zeqi Huang; Nan Li; Ying Ma; Jianshan Ye (Chemical Engineering Journal, 2026)

Automated approach to identifying wildfire plumes using S-band polarimetric radar observations - Hong Wang; Hua Deng; Haojia Li; Binqi Zhao; Cui Ye (Atmospheric Research, 2026)

The advances and implications on shoal-water deltaic sedimentology - Xin Li; Shiqiang Xia; Nadeem Ahmad; Dongqing Ye; Wei Wu; Jimei Deng; Hong Li (Applied Geophysics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Aeromonas hydrophila induces mitophagy for intracellular survival through its secreted effectors in the splenic macrophages of grass carp (Ctenopharyngodon idella) - Xiaoyu Ma; Rong Ye; Wansong Li; Zhenhong Ou; Hong Zhou (Fish & Shellfish Immunology, 2026)

Controlled synthesis of micro-flexible fluorine-neodymium nanosheets for separation membranes with enhanced properties - Shurui Han; Hui Ye; Jing Lv; Xiaojian Fu; Hong Li; Yuzhong Zhang (Chemical Engineering Journal, 2026)

Synergistic engineering of a MYB transcription factor boosts fucoxanthin and biomass co-production in the diatom Phaeodactylum tricornutum - Ting-Bin Hao; Mei-Qi Li; Rongxiang Guo; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Algal Research, 2026)

Variation characteristics and segment differences of urban heat exposure risk in continuous time series: A comprehensive synchronous comparison of daily and hourly scales - Junmao Zhang; Xia Yao; Meixia Lin; Tao Lin; Yuan Chen; Wenhui Li; Hongkai Geng; Yicheng Zheng; Zixu Jia; Hong Ye; Guoqin Zhang (Landscape and Urban Planning, 2026)

A deep stacked autoencoder for magnetotelluric data denoising via end-to-end time-domain noise mapping - Jin Li; Jingkun Ye; Nianchun Li; Dian Hong; Chaojian Chen (Journal of Applied Geophysics, 2026)

Broad band near-infrared perovskite phosphor in the NIR-I and NIR-II windows through crystal field modulation and ions doping strategy - Tao Yin; Junhua He; Hongcheng Zhao; Caiqi Ye; Yiqi Yin; Nian Fu; Fenghe Wang; Guoyi Dong; Li Guan; Hong Zhang; Xu Li (Chemical Engineering Journal, 2026)

Iatrogenic plasticizer Di(2-ethylhexyl) phthalate (DEHP) exposure increases Sepsis mortality risk: Machine learning implicates monocyte-driven immune dysregulation - Jun-jie Gao; Li-zhu Huang; Tao Wang; Yun-long Zhang; Kai Ye; Wei-hua Lu; Pu-hong Zhang (Toxicology and Applied Pharmacology, 2026)

The evaluation to combined toxic effects of polypropylene microplastics and benzo[a]pyrene on macrophage cells - Ye-xuan Zhang; Rui Hou; Si-si Chen; Xue-wen Guo; Hong-juan Chen; Li Mao; Wei-juan Zheng; Hong-zhen Lian (Science of The Total Environment, 2026)

Five new prenylated flavonoids derivatives from Dysosma versipellis and their DPPH radical scavenging activity - Meng Zhang; Hong-Yun Bai; Ling-Yu Ye; Xiao-Ke Zheng; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Shen Liang; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry Letters, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Efficient photocatalytic production of hydrogen peroxide via covalent triazine frameworks under visible light illumination - Xiahong Xu; Yan Sui; Wentong Chen; Xiaodan Li; Wei Huang; Huixian Ye; Yuntong Li; Hong Zhong (Journal of Environmental Chemical Engineering, 2026)

Flow-driven piezo-photocatalytic synergy in Bi24O31Br10/β-PVDF membranes: Interfacial electron transfer-mediated enhancement of tetracycline degradation - Yixuan Hong; Yanhua Cui; Zengkai Wang; Jian Ye; Chunyan Li; Weilong Shi; Chao Yan (Journal of Environmental Chemical Engineering, 2026)

Environmental effects of Shenhu gas hydrate trial production: A perspective on carbon cycling in shallow sediments - Taiheng Lv; Cuiling Xu; Zhilei Sun; Hong Cao; Xilin Zhang; Wei Geng; Ye Chen; Sinan Xu; Dong Zhang; Yucheng Zhou; Shixing Li; Yunbao Sun; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Bacillus velezensis-derived methylmalonic acid inhibits Aspergillus flavus growth and aflatoxin biosynthesis by interfering with tryptophan metabolism - Ming Li; Qin Han; Xiulan Zhao; Yuxuan Hong; Ye Zhu; Can Liu; Jinyan Chai; Ling Cheng; Xiaofeng Yue; Xiaoqian Tang; Jing Mao; Qi Zhang; et al. (Chemical Engineering Journal, 2026)

High-density microfluidic Chip (HD-μChip) for multiplex detection in miniaturized immunoassays - Yiran He; Min Wang; Zhaoxu Luo; Xiaodong Ma; Min Jiang; Yanhua Chen; Jingyi Qin; Yayun Gu; Xin Li; Ying Shi; Hong Wang; Ye Shen; et al. (Chemical Engineering Journal, 2026)

Molecular trade-offs in methane adsorption-diffusion behavior induced by matrix acidification of bituminous coal - Jiexin Lu; He Li; Shiliang Shi; Quanle Zou; Yi Lu; Yidu Hong; Qing Ye (Fuel, 2026)

Cold plasma precipitation of sarcoplasmic proteins from surimi wastewater: Differential structural modifications of biphasic proteins mediate dynamic transformation - Qiang Li; Jianfeng Lu; Zhicheng Cai; Yuan Song; Hong Wang; Tao Ye; Lin Lin; Wenhua Miao; Bin Zheng; Changhu Xue (Food Chemistry, 2026)

Efficient capillary electrophoretic analysis of anthraquinones and phenolic acids in functional foods using a novel deep eutectic solvent–in–deep eutectic solvent microemulsion - Kai-Yang Fan; Shi-Qi Niu; Tian Zhang; Jun Cao; Li-Hong Ye (Food Chemistry, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Effect of the protective clothing microenvironment on human thermal comfort in high-humidity environments - Fang Wang; Ye Tian; Guyao Zhang; Hong Liu; Xianfei Liu; Jicheng Li; Jun Zhang; Chaowen Deng; Xiaohan Zhang (Energy and Buildings, 2026)

Deciphering the architecture of complex karst conduit networks in mountainous tunneling areas and its implications for water inrush risk using aquitard-constrained multi-source data - Xulei Guo; Yifan Chen; Jingwen Li; Mingming Luo; Junyi Yang; Benxin Jiang; Jingyi Xu; Yufei Zhang; Jiaqi You; Tiantong Zhou; Ye Kuang; Hong Zhou; et al. (Engineering Geology, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Transgene-free genome editing in citrus and poplar meristem tissues via biolistic ribonucleoprotein delivery of CRISPR-Cas9 - Dhiôvanna Corrêia Rocha; Miracle Osazee Omoregbee; Weifeng Luo; Hong Fang; Qiushi Ye; Yanxin Liu; Gen Li; Juliet Mascoveto; Alessandra Alves de Souza; Gary Coleman; James N. Culver; Yiping Qi (Plant Cell Reports, 2026)
Key message Biolistic particle bombardment was used to deliver CRISPR-Cas9 ribonucleoprotein complexes (RNP) into the shoot apical meristem tissue of citrus and axillary meristem tissue of poplar, generating directed mutations in target genes. Abstract The use of meristematic tissues offers a strategic approach to genome editing in woody species, especially those that are recalcitrant to conventional tissue culture, as these regions contain totipotent, highly regenerative cells capable of giving rise to whole plants. Here, we employed biolistic delivery of genome-editing reagents into theshoot apical meristem (SAM) of citrus and the axillary meristems (AXM) of poplar. The system was first validated using a GFP expression construct and subsequently applied for targeted genome editing. In citrus, edited plants were obtained at the CsNPR3 locus exclusively through the delivery of CRISPR/Cas9 ribonucleoproteins (RNPs), whereas plasmid-based vectors were unsuccessful. Similarly, genome editing in poplar was achieved using RNPs targeting the Pt4CL1 gene. Although chimeric events were detected, this approach provides a feasible and innovative framework for producing transgene-free edited perennial plants.

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

Diffusion dynamics coupled with in situ etching enable controlled growth of InAs quantum dots with narrow SWIR emission - Feng Zhao; Hong-Wei Duan; Ye Wang; Zong-Shuo Liu; Zhou Li; Sanxia Yin; Shulin Chen; Ya-Kun Wang; Liang-Sheng Liao (Science Bulletin, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Intelligent Control System for Particulate Matter: Real-Time Monitoring and Pollution Source Identification for Enhanced Efficiency - Peng Shi-Tao; Li Long-Chuang; Ye Yin; Hong Ning-ning; Zhang Jing; Chen Zi Jing; Du Hong-Bo (Water, Air, & Soil Pollution, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Comprehensive micellar / reversed-phase two-dimensional liquid chromatography for separation and identification of phenolic compounds in herbal tea by multivariate statistical analysis - Qian-Xue Shen; Yi-Wen Wu; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Analytica Chimica Acta, 2026)

ZNF384-regulated SLC31A1 expression promotes tumor proliferation and invasion in breast cancer - Tianzi Hong; Wenlian Li; Qingwei Wang; Zeyi Ye; Yueqin Xu; Bo Yang; Jiaxing Chen; Weibin Lian; Chuan Wang (Molecular and Cellular Biochemistry, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Spatial distribution and ecological risk assessment of heavy metals in sediment around the coastal oyster reefs in Guangdong, China - Xiaomin Li; Jianping Ye; Xin'an Yue; Hua Wang; Yaohui Chen; Zihua Zhou; Hong Qiu; Jingxin Liu; Zhongyuan Wang; Shengyong Li; Yang Gao; Xiaoshou Liu; et al. (Marine Pollution Bulletin, 2026)

Molecular insights into bioinhibitory toxicity driven by dissolved organic matter transformation during wastewater reclamation - Hong Liu; Jianfeng Ye; Jinxu Zhang; Yu Chen; Yi Zhu; Yongjiao Yi; Zhengyang Li; Wei Jin; Zuxin Xu (Water Research, 2026)

Ketamine's brain spatial distribution and metabolic effects in a mouse model of anxiety: Insight into in situ mass spectrometry imaging and metabolomics methods - Hong Yang; Weihao Fan; Xinyu Yang; Ying Wei; Li Xiao; Hongkun Yang; Linzhi Jiang; Jian Li; Kaiting Shi; Shuang Zhao; Lin Yang; Yi Ye; et al. (NeuroToxicology, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

Anti-epileptic effect of saikosaponin a by inhibiting ferroptosis via the IL-17/Akt/ERK signaling pathway in the temporal lobe epilepsy model - Ping-Ping Li; Wen-Wen Wang; Jing-Tao Wang; Zi-Ao Xu; Xue-Fei Ji; Liao Guan; Lei Ye; Hong-Wei Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Glaucocalyxin A Promotes Spinal Cord Repair By Nrf2/HO-1 Pathway Activation to Suppress AIM2 Inflammasome Formation - Ze Li; Jiajing Ye; Zhiyu Fang; Xinyu Wu; Fang Tang; Ting Jiang; Yuhang Gong; Yuxuan Bao; Binbin Zheng; Huaxing Hong; Zhenghua Hong (Molecular Neurobiology, 2026)

Harnessing lactobacillus : a probiotic revolution in combating metabolic dysfunction-associated steatotic liver disease - Minwen Gu; Qing Hong; Jie Cui; Wenhui Li; Jian Zhang; Ye Sun; Jinchi Jiang; Yonghong Hu (Critical Reviews in Food Science and Nutrition, 2025)

Unveiling the effect of Fe(III) and sulfate on ammonium oxidation under anaerobic condition: interactions and extracellular electron transfer - Weizhuo Ye; Jiaqi Yan; Jia Yan; Qixing Ji; Lei Huang; Meng Li; Hongguo Zhang; Shuyuan Hong; Jinying Cai (Water Research, 2025)

Pathways for mitigating urban thermal environment through 3D compact form regulation: A novel machine learning model for exploration and application - Ranran Ji; Yufeng Chi; Yun Zhang; Xian Wu; Zhiyuan Li; Yujia Bai; Ruiming Zhang; Guoqin Zhang; Hong Ye (Urban Climate, 2025)

Performance assessment of aluminum slitted finned tube heat exchangers with small tube diameters - Fang Wang; JiCheng Li; ChaoWen Deng; XianFei Liu; Jun Zhang; Ye Tian; Hong Liu; Senqing Zhuo; Wei Guo (International Journal of Refrigeration, 2025)

Non-ionic microemulsion extraction and in situ cloud point liquid-liquid microextraction of flavonoids and carotenoids from functional food - Qian-Xue Shen; Yan-Hua Jiao; Ting-Hong Fei; Jun Cao; Li-Hong Ye (Food Chemistry, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Multiband bipolar photoresponse in Cu@CuOx@a-Ga2O3 core-shell heterostructure-based self-powered photoelectrochemical-type photodetector for secure underwater optical communication - Yixin Sun; Yan Tang; Xiuhong Jiang; Aijiang Yan; Jin Zhao; Yuchuan Wang; Jiangshuai Luo; Jili Jiang; Ke Ding; Hong Zhang; Honglin Li; Di Pang; et al. (Chemical Engineering Journal, 2025)

Optical Fiber Sensor Based Transportable Active Seismic Survey System Solution to OSI - Qin Li; Zhaoli Li; Zhifeng Wang; Ye Lang; Hong Liu; Wei Zhao; Chenyu Yi; Jing Yang; Peng Li (Pure and Applied Geophysics, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Enhanced nattokinase production by optimized fermentation conditions of douchi-derived Bacillus subtilis natto NK11 and evaluation of its thrombolytic activity - Yanxin Ye; Wenjuan Yue; Ruoxue Hu; Xiaokang Li; Leilei Li; Yanyan Chen; Bingbing Li; Zhi Li; Jun Hong (Antonie van Leeuwenhoek, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Unleashing the potential of biotechnological strategies for the sustainable production of microalgal polysaccharides - Srinivasan Balamurugan; Da-Wei Li; Xiang Wang; Hong-Ye Li (Critical Reviews in Food Science and Nutrition, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Quantitative evaluation method for the winding package deformation of non-metallic armored CTD cable on the multi-layer winch - Shanying Lin; Zehua Li; Wenhua Li; Haoran Ye; Lei Hong; Fei Wang (Ocean Engineering, 2025)

Different AOM processes driving the formation of carbonate crusts and nodules in the Okinawa Trough - Yucheng Zhou; Hong Cao; Zhilei Sun; Wei Geng; Chenhui Liu; Xilin Zhang; Cuiling Xu; Taiheng Lv; Shixing Li; Ye Chen; Xuejun Jiang; Dong Zhang; et al. (Marine and Petroleum Geology, 2025)

Dual-tracer analysis of stable isotopes and thermal signals to quantify groundwater residence times in karst rhythmic spring systems - Xulei Guo; Mingming Luo; Jingwen Li; Yifan Chen; Ye Kuang; Cong Jiang; Hong Zhou (Journal of Hydrology, 2025)

Variations in oxidation profiles of myofibrillar protein from silver carp (Hypophthalmichthys molitrix) by frozen storage and hydroxyl radicals: A proteomic insight - Longteng Zhang; Juan You; Yuhui Ye; Yulong Bao; Yuqing Tan; Hui Hong; Qian Li (Food Chemistry, 2025)

Anti-interference detection of Pb (II) in seawater enabled by a photo-electrostatic ZnFe2O4/MoS2 heterojunction electrode - Shu Huo; Rong Guo; Gengchen Li; Hong Liu; Wenbo Hang; Tingting Liu; Ye Ma; Minggang Zhao (Chemical Engineering Journal, 2025)

Integrative machine learning and molecular insights into ZEN degradation by Apiotrichum mycotoxinivorans - Zhi-Kai Yang; Yun Huang; Xue-Ling Huang; Dan Huang; Liang Peng; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Chemical Engineering Journal, 2025)

Materials and duration of mulching mediate soil and fruit quality in citrus orchard - Lei Yang; Min Wang; Jianjun Yu; Shuang Li; Haihong Tan; Yang Chen; Juhong Liu; Sijia Ye; Jinhui He; Lin Hong (Plant and Soil, 2025)

Metal-organic framework ZIF-67 derived Co@CN catalysts for the promising generation of hydrogen from ammonia decomposition - Tianxiang Li; Xiaofeng Gu; Qing Wang; Kailong Zhang; Wanze Li; Hong Du; Hewen Liu; Emin Aili; Yufang Ye; Xiao Chen (Fuel, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

Metabolic activation and cytotoxicity of bavachin mediated by CYP3A in mice - Tingmin Ye; Chunping Tang; Dandan Yang; Qing Zhang; Yufen Liao; Jie Dai; Hong Tang; Changqiang Ke; Ying Peng; Yang Ye; Weiwei Li; Jiang Zheng (Chemico-Biological Interactions, 2025)

Biochar alleviates adverse effects of polystyrene microplastics on anaerobic digestion performance of food waste and antibiotic resistance gene propagation - Feng Wang; Ye Li; Linjie Zhang; Yinglong Su; Yan Zhang; Seungkwan Hong; Min Zhan; Bing Xie (Bioresource Technology, 2025)

Health impacts and drivers of long-term ozone and nitrogen dioxide exposure in urban China - Zhaoli Yang; Fangliang Li; Rongmin Ye; Huiping Ge; Hongyu Li; Shulian Zhang; Jiaxin Wang; Yuan Zhao; Hong Gao; Tao Huang; Jianmin Ma (Atmospheric Pollution Research, 2025)

Commensal Bacillus pumilus SE5-Derived Peptidoglycan and Lipoteichoic Acid Showed Synergistic Effects in Improving Growth, Immunity, and Intestinal Health of Grouper (Epinephelus coioides) - Jian-Ming Xu; Guo-He Cai; Jie Li; Hong-Ling Yang; Ji-Dan Ye; Yun-Zhang Sun (Probiotics and Antimicrobial Proteins, 2025)

Exploring the Role of Microglia Activation in Ischemia Stroke Based on the circDnajc1/miR-27a-5p/C1qc Signaling Axis - Shuangping Li; Qingping Ye; Yumeng Li; Jingjing Li; Chao Yu; Sujun Xue; Lijuan Zhang; Daiyin Peng; Shizhong Hong; Xianchun Duan (Molecular Neurobiology, 2025)

Tongxinluo alleviates myocardial ischemia–reperfusion injury by inhibiting the pyroptosis of endothelial cells via the NLRP3/Caspase-1/GSDMD signaling pathway - Xuan Wu; Yun-long Hou; Tong-xing Wang; Li-ping Chang; Hong-ru Zhou; Ming-ye Wang; Yi-ling Wu (Journal of Molecular Histology, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

A novel early warning method for thermal runaway of lithium-ion batteries based on mechanical stress signal - Chenrui She; Chaoshi Liu; Yuxuan Li; Xiaoyang Wang; Hong Ye; Chunmei Zeng; Wenxin Mei; Qingsong Wang (Process Safety and Environmental Protection, 2025)

Post-harvest precooling technology and fresh-keeping mechanism of fruits and vegetables: A review - Oujun Dai; Yueguang Wang; Meining Li; Wanxin Hong; Xin Lei; Ziwei Ye; Jie Pang; Yilan Sun (Postharvest Biology and Technology, 2025)

Unveiling the biogeography of ammonia-oxidizing prokaryotes (AOPs) in the South China Sea: Novel lineages and their ecological niches - Yuexi Ma; Cuihong Jiang; Jiapeng Wu; Xiaoyi Li; Fei Ye; Xiaomei Shen; Yu Wang; Yiguo Hong (Marine Environmental Research, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Glycerol enhanced simultaneous selenite bioremediation and astaxanthin biosynthesis in Haematococcus lacustris - Yu-Hu Jiao; Zhong-Hong Zhang; Yu-Hong Liu; Yan Huang; Meng-Ting Jiang; Yong-Teng Zhao; Xinfei Xie; Wei-Dong Yang; Hong-Ye Li; Lei Cui; Xiang Wang (Journal of Hazardous Materials, 2025)

Soil mesofauna bacterial diversity: Insights from cultured collembolans, enchytraeids, and mites species - Bo-Wen Liu; Jing Wen; Shuai-Fei Ye; Jia-Jia Gu; Ming-Xin Li; Xiao-Bo Xiong; Zong-Zheng Liang; Hong-Tao Wang (Food Webs, 2025)

Simulation-guided plasma surface engineering for enhanced triboelectric Nanogenerator performance - Hong Yu; Haonan Ma; Zuying Huang; Mengya Lin; Junming Chen; Ruibin Wu; Ye Tao; Chengrun Li; Ruijia Yang; Xiaozhen Du (Chemical Engineering Journal, 2025)

Longitudinal relationships between changes in post-COVID mental fatigue and neuropsychiatric symptoms across distinct recovery trajectories - Wenrui Bao; Siyuan Chen; Ningkun Hong; Gengchen Ye; Chiyin Li; Jingmei Xie; Peng Li; Heng Li; Yang Wang; Jixin Liu; Xuan Niu; Yuchen Zhang (Inflammopharmacology, 2025)

Correction: How does central-local policy implementation deviation affect urban residents’ green consumption behavior? A multi-agent simulation considering environmental awareness and social interaction - Xiangyang Ye; Ruyin Long; Hong Chen; Shiyan Jiang; Yunhao Sun; Qian Li; Junling Liu (Environment, Development and Sustainability, 2025)

How does central-local policy implementation deviation affect urban residents’ green consumption behavior? A multi-agent simulation considering environmental awareness and social interaction - Xiangyang Ye; Ruyin Long; Hong Chen; Shiyan Jiang; Yunhao Sun; Qian Li; Junling Liu (Environment, Development and Sustainability, 2025)

Acute alkalinity stress triggers kidney histopathology, oxidative-immune dysregulation, and MAPK/TGF-β signaling pathways activation in Scatophagus argus - Lingwei Kong; Adili Abudu; Lei Yang; Minghui Ye; Yulei Zhang; Yucong Hong; Huapu Chen; Guangli Li; Gang Shi; Changxu Tian (Aquaculture, 2025)

Leveraging artificial intelligence to quantify slope rainfall sensitivity for refining regional landslide rainfall thresholds - Yuhang Zhu; Kunlong Yin; Ye Li; Haoran Yang; Hong Chen; Chao Zhou; Samuele Segoni (Engineering Geology, 2025)

SIRT1 Attenuates Neuropathic Pain via CDK5-Kalirin-7 Signaling Pathway in Type 2 Diabetic Rats - Cishan Xie; Yannan Cao; Yujing Shen; Shishu Wu; Junwu Wang; Xiuying Ye; Ning Wei; Hong Cao; Jun Li (Molecular Neurobiology, 2025)

Characterization and functional analysis of CsTLR13M/13S, two novel teleost toll-like receptor 13 in antimicrobial immunity - Ji-xing Feng; Sheng-jia Wang; Hong-ye Wang; Xue-peng Li (Aquaculture, 2025)

An adaptive control method of non-metallic armoured Optical-electrical cable winch system in Oceanographic Research Vessel based on three-dimensional laser scanning point cloud - Haoran Ye; Hongjie Guo; Wenhua Li; Shanying Lin; Gen Li; Lei Hong (Ocean Engineering, 2025)

The tolerance mechanism of diarrhetic shellfish toxins mediated by the extracellular regulated protein kinase (ERK) pathway in the mussel Perna viridis - Jin-jin Lv; Yu-jie Liu; Yan-hang Mo; Li-yan Deng; Yang Liu; Hong-ye Li; Li Zhang; Wei-dong Yang (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Transcriptomic analysis to identify differentially expressed genes of abdominal fat (AF) and breast muscle (BM) tissues based on RNA-seq in Zhijin white goose - Zhonglong Zhao; Yong Zhang; Hong Yang; Zhiwei Wang; Zhaobi Ai; Runqian Yang; Tiansong Wang; Li Ye; Chang Shu (Tropical Animal Health and Production, 2025)

Tiered ecological risk assessment of perfluoroalkyl acid mixtures based on relative potency factor and species sensitivity distribution - Jianming Jiang; Xun Wang; Xi-Long Zhang; Hui Liu; Wen-Jun Hong; Minjie Li; Liang-Hong Guo; Cheng Ye; Hai-Wei Luo (Environmental Geochemistry and Health, 2025)

Remarkable metabolic reconfiguration due to three classical nitrogen sources in Gracilariopsis lemaneiformis (Rhodophyta) - Wenkang Fan; Chunyou Yang; Dingzhi Song; Peilin Ye; Honghao Liang; Chunping Huang; Muhamad Syaifudin; Chenhui Zhong; Tangcheng Li; Hong Du (Algal Research, 2025)

Rakicidin J and K, two cytotoxic and antibacterial cyclic depsipeptides from the marine bacterium Micromonospora chalcea - Li Chen; Lijun Xie; Jian Zhou; Dongsheng Fang; Honglei Jiang; Wei Liu; Yuqiu Ye; Wei Zhao; Hong Jiang; Feng Lin (Natural Product Research, 2025)

Tomato DC1 domain protein SlCHP16 interacts with the 14–3-3 protein TFT12 to regulate flower development - Guobin Li; Jiafa Wang; Licheng Xiao; Chunli Zhang; Dedi Zhang; Guo Ai; Minghua Yao; Changxing Li; Zonglie Hong; Zhibiao Ye; Junhong Zhang (Plant Science, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Conductive substance as game-changer in mediating bioelectrocatalytic nitrogen fixation: The crucial role of extracellular polymeric substances - Lei Li; Chao Wang; Mingqiu Hong; Piao Chen; Guocheng Huang; Wenzhi Gu; Jie Ye; Shungui Zhou (Journal of Environmental Chemical Engineering, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Revealing the miscibility chemistry of ionic liquids in water-in-salt electrolytes toward high-voltage and high-temperature aqueous potassium-ion supercapacitors - Jianchao Chen; Guanghao Zhang; Hong Zhang; Shuxian Zhang; Qingyu Li; Chunyan Zhu; Xiaoge Man; Zhiwei Zhang; Yuanchang Shi; Tao Li; Ye Han; Mengqi Zhang; et al. (Science Bulletin, 2025)

Iron scrap derived nano zero-valent iron/biochar activated persulfate for p-arsanilic acid decontamination with coexisting microplastics - Zihan Shu; Hailan Yang; Shujing Ye; Hong Li; Zhiming Yang; Chuang Li; Xiaofei Tan; Shaobo Liu; Hou Wang (Journal of Environmental Sciences, 2025)

Thermoelectric performance in Ag2Se nanocomposites: The role of interstitial Ag and Pb orbital hybridization - Khak Ho Lim; Yuxuan Xia; Lixiang Xu; Mingjun Zhao; Mingquan Li; Ye Cheng; Jiale Mao; Shuang Wang; Lei Chen; Sai Wing Tsang; Pingwei Liu; Qingyue Wang; et al. (Chemical Engineering Journal, 2025)

Unveiling novel oxygen-dependent docosahexaenoic acid biosynthesis pathway in Crypthecodinium cohnii via dual-function △4-fatty acid desaturases - Yi-Tong Yao; Xiao Zhang; Chen-Yu Wang; Yu-He Zhang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Bioresource Technology, 2025)

Skeletal muscle-specific Bambi deletion induces hypertrophy and oxidative switching coupling with adipocyte thermogenesis against metabolic disorders - Xiangping Yao; Xudong Mai; Ye Tian; Yifan Liu; Guanghui Jin; Ze Li; Shujie Chen; Xiaoshuang Dai; Liujing Huang; Zijing Fan; Guihua Pan; Xiaohan Pan; et al. (Science China Life Sciences, 2025)

Real-Time Fault Diagnosis of Mooring Chain Jack Hydraulic System Based on Multi-Scale Feature Fusion Under Diverse Operating Conditions - Yujia Liu; Wenhua Li; Haoran Ye; Shanying Lin; Lei Hong (Journal of Marine Science and Engineering, 2025)
The condition monitoring of mooring equipment is an important engineering reliability issue during the operation of a floating production storage and offloading unit (FPSO). The chain jack (CJ) is the key equipment for powering the mooring chain in a spread mooring system. Under complex and dynamic marine operating conditions, different severity faults in the CJ hydraulic system display distinct time-scale characteristics. Hence, this paper proposes a real-time fault diagnosis method of the CJ hydraulic system based on multi-scale feature fusion. Firstly, the model incorporates a convolutional neural network (CNN) layer to extract localized spatial features from multivariate time-series data, effectively identifying fault patterns over the associated short intervals. Subsequently, the bidirectional long short-term memory (BiLSTM) layer is introduced to construct a dynamic temporal model to comprehensively capture the evolution of the fault severity. Finally, a multi-scale global attention mechanism (GAM) emphasizes persistent fault behaviors across time scales, dynamically prioritizing relevant features to improve diagnostic accuracy and model interpretability. The study results indicate that the proposed model’s accuracy improves by 7.36% over the CNN-GAM for 11 failure modes, up to 99.34%. This study contributes to the safe operation of an FPSO by guiding monitoring CJ operations under different load conditions.

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

MXene-based soft robots with multi-stimulus response and energy storage - Xiaoyan Tang; Qiantao Huang; Di Pang; Yuchuan Wang; Honglin Li; Yan Tang; Lijuan Ye; Hong Zhang; Wanjun Li (Chemical Engineering Journal, 2025)

Mussel-inspired integrated functional 3D printed scaffolds with molybdenum disulfide nanoflowers for tumor therapy and bone reconstruction - Lan Li; Rongcan Wu; Ruchen Hong; Xiaolong Chen; Tingting Huang; Siyi Huang; Xianglei Mo; Zhiyi Wang; Wenge Liu; Yanjin Lu; Ye Wu; Jinxin Lin (Chemical Engineering Journal, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Electrochemical and interfacial studies on the oxidation of pyrite at high altitude area - Yan Miao; Guangke Ye; Binbin Li; Hong Zheng; Guofan Zhang (Minerals Engineering, 2025)

Assessing the effectiveness of green consumption policy in China: Evidence from social media data - Junling Liu; Ruyin Long; Hong Chen; Lu Qin; Han Huang; Qian Li; Xiangyang Ye (Journal of Environmental Management, 2025)

A press-actuated slidable microfluidic colorimetric biosensor for Salmonella detection utilizing nickel mesh sheet and MIL-88@Pd/Pt nanoparticles - Jing Yuan; Lei Wang; Hong Duan; Siyi Ye; Ying Ding; Yanbin Li; Jianhan Lin (Food Chemistry, 2025)

Green fabrication of polyamide nanofiltration membranes with ultra-low chemical consumption by vacuum filtration-spraying assisted interfacial polymerization - Hong-Yu Fan; Cheng-Ye Zhu; Yu-Ren Xue; Jin-Bo Li; Chao Zhang; Tian-Yu Zhang; Li-Wu Fan; Zhi-Kang Xu (Desalination, 2025)

Ultralow frequency waves in the South Atlantic anomaly: Application of FY-3E observations - Li Li; Qiugang Zong; Xuzhi Zhou; Ying Liu; Robert Rankin; Shan Wang; Yongfu Wang; Xiangqian Yu; Jie Ren; Zikang Xie; Hong Zou; Yuguang Ye; et al. (Science China Earth Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic impact of Gracilaria bailinae extracts on photosynthesis and metabolism in Phaeodactylum tricornutum - Li-Gong Zou; Fu-Fang Wen; Xiao Zhang; Gang Li; Qing Wang; Hong-Ye Li; Yu-Feng Yang (Marine Environmental Research, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

Intelligent sensing platform based on europium-doped carbon dots for dual-functional detection of ciprofloxacin/Ga3+ and its tracking in vivo - Le Liang; Su-qian Cai; Yan-li Leng; Chan Huang; Yong-qing Liu; Ye Wang; Li Luo; Mei Han; Xiao-hong Li; Xiao-hua Cai (Journal of Hazardous Materials, 2025)

High conductivity, low-hysteresis, flexible PVA hydrogel multi-functional sensors: Wireless wearable sensor for health monitoring - Ye Yu; Zhijian Zhou; Hong Ruan; Yuqi Li (Chemical Engineering Journal, 2025)

Shear strain prediction of reservoir landslide based on FBG monitoring and bagging-MLP algorithm - Jia Wang; Hong–hu Zhu; Xiao Ye; Feng Tian; Wei Zhang; Hou–zhi Li; Hua–fu Pei (Bulletin of Engineering Geology and the Environment, 2025)

Medium modification of Cynanchum wilfordii adventitious root culture for the production of C21 steroidal glycosides, polysaccharides, and polypeptides using orthogonal design methods - Han-Xi Li; Yu-Qing Guo; Wei-Qi Ye; Zhong-Yu Zhou; Ling-Hong Bai; Xuan-Chun Piao; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Radiofrequency affects the decrystallization efficiency and physicochemical properties of rape honey via crystal structure modification and inactivating enzyme - Shi-Ye Luo; Jia-Li Tao; Yan-Xiang Bi; Hong-Wei Xiao; Hua-Lei Chen; Xiang-Xin Li; Yin-Chen Wang; Xiao-Ming Fang (Food Chemistry, 2025)

Seismic response of a long shield tunnel crossing through multiple soil deposits - Zhi Ye; Yongchi Li; Lihua Li; Wenjin Xu; Hong Wu; Yu Miao; Huabei Liu (Computers and Geotechnics, 2025)

Manipulating weak interactions between host/guest and analytes in Cu(I)-cluster-based MOF for fluorescent gas sensing towards chlorinated volatile organic compounds - Yunfang Zhao; Yangxingyu Ye; Zhiyuan Wu; Jiaxin Jiang; Zhijia Li; Hang Lei; Feilong Jiang; Lian Chen; Maochun Hong (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Starch/polyacrylamide hydrogels with flexibility, conductivity and sensitivity enhanced by two imidazolium-based ionic liquids for wearable electronics: Effect of anion structure - Ziling Zhang; Lu Lu; Bingbing Hong; Qichao Ye; Li Guo; Chao Yuan; Bo Liu; Bo Cui (Carbohydrate Polymers, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

An investigation of aggregate breakup of structured soft clay under one-dimensional compression based on FESEM images - Chao Ye; Qian Cheng; Hong Sun; Fujun Niu; Yue Li (Bulletin of Engineering Geology and the Environment, 2025)

Similar tolerance of urban birds towards both benign human and lethal cat predators - Hong-Yan Ye; Jing Yu; Kang Hong; Ya-Lian Li; Jin-Ming Zhao (Journal of Ornithology, 2025)

MshK mutation reduces pathogenicity of Aeromonas veronii by modulating swimming ability, biofilm formation capacity, pili structure and virulence gene expression - Jiahui Lu; Jinming Wei; Kemei Liu; Bei Wang; Liping Zhang; Yongyao Yu; Yun Li; Hua Ye; Hong Li; Ronghua Wu (Aquaculture, 2024)

A green and effective glucoside surfactant assisted micellar electrokinetic chromatography for the separation of phenolic compounds from medicinal plant using response surface methodology - Qian-Xue Shen; Yan-Hua Jiao; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Benign water quality and phytoplankton status during the operation of Guishan offshore wind farm in the Pearl River Estuary, China - Yuankai Hong; Ziyun Liu; Shubing Li; Yan Long; Jiong Gao; Ren Hu; Jinshao Ye (Regional Studies in Marine Science, 2024)

Highly efficient adsorption and removal of phthalate esters by polymers of intrinsic microporosity - Xiaoya Sun; Jun Wang; Jun Kang; Jingyi Sun; Shunying Li; Yingying Zhang; Hong Ye; Shuangyang Li; Xianren Zhang (Journal of Hazardous Materials, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

CRISPR-based genetic screens advance cancer immunology - Yuanfang Cao; Xueting Li; Yumu Pan; Huahe Wang; Siyu Yang; Lingjuan Hong; Lupeng Ye (Science China Life Sciences, 2024)

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Magnetic adsorbents for removal of bisphenol A: Design strategies of materials and adsorption mechanisms - Ruobing Jia; Yingying Zhang; Shunying Li; Jun Wang; Jun Kang; Qiangqiang Xu; Hong Ye (Chemosphere, 2024)

Tower-based profiles of wintertime secondary organic aerosols in the urban boundary layer over Guangzhou - Yao Li; Hong Ren; Shengzhen Zhou; Chenglei Pei; Min Gao; Yuxuan Liang; Dian Ye; Xijing Sun; Fenghua Li; Jun Zhao; Jian Hang; Shaojia Fan; et al. (Science of The Total Environment, 2024)

Revealing conflict risk between landscape modification and species conservation in the context of climate change - Runjia Yang; Sha Chen; Xinyu Dong; Kechao Wang; Tingting He; Hong Chen; Xiaoya Li; Yanmei Ye; Wu Xiao (Journal of Cleaner Production, 2024)

Preparation of novel magnetic ethylene glycol dimethacrylate-based molecularly imprinted polymer for rapid adsorption of phthalate esters from ethanol aqueous solution - Yuanhao Zhou; Shunying Li; Xiaoya Sun; Jun Wang; Haoxiang Chen; Qiangqiang Xu; Hong Ye; Shuangyang Li; Shengpeng Shi; Xianren Zhang (Environmental Pollution, 2024)

An Eco-friendly β-cyclodextrin/Stilbene-Integrated supramolecular material Realizes the effective treatment of bacterial diseases via enhancing the biofilm eradication and Agrochemical bioavailability - Li Zhou; Yazhen Chen; Jinghan Yang; Yaling Duan; Huiqin Gong; Haojie Ye; Ya Hong; Min Liu; Gefei Hao; Fengpei Du; Peiyi Wang (Chemical Engineering Journal, 2024)

Study on the effects of electrode volume fraction and electrode particle radius on dynamic electrochemical-thermal-aging coupling characteristics of lithium cell based on cylindrical cell design method - Xu-Dong Yuan; Zhen-Kai Xiong; Lian-Cheng Li; Chuan-Ye Tang; Qi-Wei Jia; Hong-Chuan Tuo; Yan Zhang (Chemical Engineering Journal, 2024)

Enhanced lipid production of Auxenochlorella pyrenoidosa using biochar-pretreated tobacco industry wastewater - Ting-Bin Hao; Zhong-Hong Zhang; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Chemical Engineering Journal, 2024)

Asymmetric structural strategy enables efficient MR-TADF emitters with low efficiency roll-off and doping-concentration insensitivity - Zhang-Li Cheng; Jie Li; Hui Wang; Feng Huang; Ying-Chun Cheng; Hao Wu; Xin Xiong; Tong-Yuan Zhang; Jia Yu; Jun Ye; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Polyamide and deep eutectic solvent assisted matrix solid-phase dispersion microextraction for strong hydrophobic compounds - Yi-Wen Wu; Xin-Ran Ma; Xin Peng; Xudong Cai; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Middle-Late Quaternary planktonic foraminifera and the upper-column sea water changes in the northern SCS during the δ13C maximum events - Ye Xu; Bao-Hua Li; Zhou-Fei Yu; Hong-Jin Chen; Qi-Mei Guo; Kai Zhang; Xiao-Yan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Novel Cu(I)/Cu(II) oxide nanowires electrode with efficient cyclic catalytic performance for electroreduction of nitrate wastewater to ammonia - Ye Du; Wenjie Liu; Changhui Zhou; Chaoyue Xie; Zhinan Dai; Jie Wang; Jia Lin; Jinhua Li; Hong Zhu; Jing Bai; Baoxue Zhou (Journal of Environmental Chemical Engineering, 2024)

Enhanced selectivity for convenient extraction of acidic mycotoxins using a miniaturized centrifugal integrated cold-induced phase separation: Determination of fumonisins and ochratoxins in cereals as a proof-of-concept study - Shuping Hu; Baoye Ye; Hong Li; Pengcheng Yan; Dawei Chen; Min Zhao (Food Chemistry, 2024)

The health and economic burden of ozone pollution on Alzheimer's disease and mild cognitive impairment in China - Kai Li; Hong Ye; Ziyu Dong; Amujilite; Meiduo Zhao; Qun Xu; Jing Xu (Environmental Research, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

Safety, pharmacokinetics, and food-effect of pivmecillinam after single- and multiple-dose in healthy Chinese subjects: a phase I study - Lu-Lu Zhang; Yi Liu; Qiong-Ye Huang; Hong-Wen Zhang; Li-Jun Xie; Juan Chen; Li Ding; Chen Zhou; Lu-Ning Sun; Yong-Qing Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Organophosphorus flame retardants in the Qiantang River of China: occurrence, source and ecological risk assessment - Wen-Jun Hong; Xi-Long Zhang; Hui Liu; Jian-Ming Jiang; Xun Wang; Minjie Li; Liang-Hong Guo; Cheng Ye; Hai-Gang Wu (Environmental Geochemistry and Health, 2024)

Development of Extubation Success Prediction Model for Mechanically Ventilated Patients with Spontaneous Cerebellar Hemorrhage - Yao Jiang; Yue Yu; Jing Fan; Lei Zhang; Yang Ye; Ying-hong Hu; Li-da Su (The Cerebellum, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Triple modal aptasensor arrays driven by CHA-mediated DNAzyme for signal-amplified atrazine pesticide accumulation monitoring in agricultural crops - Jintong Liu; Na Li; Linyao Ye; Lin Zhou; Guanghao Chen; Jie Tang; Heng Zhang; Hong Yang (Journal of Hazardous Materials, 2024)

Impact of butylparaben on growth dynamics and microcystin-LR production in Microcystis aeruginosa - Zhong-Hong Zhang; Jian-Wei Zheng; Si-Fen Liu; Ting-Bin Hao; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Environmental Research, 2024)

SS-31 mitigates oxidative stress and restores mitochondrial function in cigarette smoke-damaged oral epithelial cells via PINK1-mediated mitophagy - Pei Ye; Hong Liu; Yao Qin; Zhiyuan Li; Zhuwei Huang; Xiangwen Bu; Qiao Peng; Ning Duan; Wenmei Wang; Xiang Wang (Chemico-Biological Interactions, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Selenium Deficiency Can Promote the Expression of VEGF and Inflammatory Factors in Cartilage Differentiation and Mediates Cartilage Injury - Xiang Meng; Xiumei Meng; Zeju He; Ye Yuan; Yong Fan; Li Yin; Yu Tong; Zheping Hong; Senbo Zhu; Qiong Zhang; Qing Bi (Biological Trace Element Research, 2024)

Mutually reinforced cancer treatment based on phototherapy combined with ferroptosis - Guan-Hong Chen; Lei Gan; Li-Yuan Tian; Bin-Xin Huang; Qiang Xiao; Yi-Jing Zhang; Mei-Tian Xiao; Bing-De Zheng; Jing Ye (Chemical Engineering Journal, 2024)

Promotion of lignin depolymerization and cellulose utilization via the coupling effects of DDQ pre-oxidation and HCOOH extraction - Jiamin Ye; Haipeng Yu; Zhiwen Jia; Wanyu Li; Linghao Li; Hong Wang; Enchen Jiang; Yan Sun; Xiwei Xu (Chemical Engineering Journal, 2024)

Effects of glycerol monolaurate on estradiol and follicle-stimulating hormones, offspring quality, and mRNA expression of reproductive-related genes of zebrafish (Danio rerio) females - Boyu Li; Limin Ye; Cheng Zhang; Ruofan Liu; Chi Wang; Xiaotian Zhang; Hong Ji; Haibo Yu (Fish Physiology and Biochemistry, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

Phylogenomics and biogeographical diversification of Collabieae (Orchidaceae) and its implication in the reconstruction of the dynamic history of Asian evergreen broadleaved forests - Hong-Yu Ji; Chao Ye; Yan-Qiong Chen; Jian-Wu Li; Arief Hidayat; Jiang-Lin Miao; Jian-Hua Li; Jian-Yong Wu; Jun-Wen Zhai; Si-Ren Lan; Xiao-Hua Jin (Molecular Phylogenetics and Evolution, 2024)

The full utilization of bagasse via deep eutectic solvent pretreatment for low-condensed lignin and cellulose smart indicator film - Wanyu Li; Jiamin Ye; Zhiwen Jia; Haipeng Yu; Linghao Li; Hong Wang; Enchen Jiang; Yan Sun; Xiwei Xu (Chemical Engineering Journal, 2024)

Physiological and genetic responses of the benthic dinoflagellate Prorocentrum lima to polystyrene microplastics - Si-Yuan Xu; Yan-Hang Mo; Yu-Jie Liu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2024)

Mechanistic enhancement of emulsification function in zein/pectin complex nanoparticles by short linear glucan - Wenhui Li; Qing Hong; Mingzhou Yu; Jie Cui; Ye sun; Li Mi; Yiyang Yu; Jinchi Jiang; Wenge Yang; Yonghong Hu (Food Hydrocolloids, 2024)

LTA and PGN from Bacillus siamensis can alleviate soybean meal-induced enteritis and microbiota dysbiosis in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Guo-He Cai; Sha Li; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Identification of a cinnamoyl-CoA reductase from Cinnamomum cassia involved in trans-cinnamaldehyde biosynthesis - Peng Ye; Jianmu Su; Jianhao Lin; Yanqun Li; Hong Wu (Planta, 2024)

Temporal variations of biological nitrogen fixation and diazotrophic communities associated with artificial seaweed farms - Pengbing Pei; Muhammad Aslam; Chunyou Yang; Peilin Ye; Xiao Ke; Zhanhua Liang; Tangcheng Li; Weizhou Chen; Hong Du (Frontiers in Marine Science, 2024)
Diazotrophic communities contribute inorganic nitrogen for the primary productivity of the marine environment by biological nitrogen fixation (BNF). They play a vital role in the biogeochemical cycle of nitrogen in the marine ecological environment. However, there is still an incomplete understanding of BNF and diazotrophs in artificial seaweed farms. Therefore, this study comprehensively investigated the temporal variations of BNF associated with Gracilariopsis lemaneiformis , as well as the diazotrophic communities associated with macroalgae and its surrounding seawater. Our results revealed that a total of 13 strains belonging to Proteobacteria and Bacteroidetes were identified as N 2 -fixing bacteria using azotobacter selective solid medium and nifH gene cloning. Subsequently, BNF and diazotrophic communities were characterized using the acetylene reduction method and high-throughput sequencing of the nifH gene, respectively. The results showed that nitrogenase activity and nifH gene abundance of epiphytic bacteria on G. lemaneiformis varied significantly among four different cultivation periods, i.e., Cultivation Jan. (CJ), Cultivation Feb. (CF), Cultivation Mar. (CM), Cultivation Apr. (CA). Among them, the nitrogenase activity and nifH gene abundance of epiphytic bacteria on G. lemaneiformis in CM were significantly higher than those in CJ, CF, and CA, indicating that the BNF of eiphytic bacteria on G. lemaneiformis was markedly enhanced. Combined with the data on environmental factors, it was found that the low concentration of nitrogen and phosphorus in CM might considerably boost the BNF of epiphytic bacteria in G. lemaneiformis . The sequencing results of the nifH gene showed that the α-diversity of diazotrophic communities associated with G. lemaneiformis and seawater in CM was higher than that in other cultivation periods. In addition, the diazotrophic communities on G. lemaneiformis were significantly different in CJ, CF, CM, and CA, and they were significantly diverse from diazotrophic communities in seawater. LEfSe analysis indicated that Rhodobacterales, Hyphomonadaceae, Robiginitomaculum , and Robiginitomaculum antarcticum within α-proteobacteria played a remarkable role in BNF in response to nitrogen nutrient deficiency. Taken together, these results provide a unique insight into the interaction between macroalgae and its epiphytic bacteria and lay a foundation for further research on the mechanism of action of nitrogen-cycling microorganisms associated with macroalgae.

Exposure to microplastics renders immunity of the thick-shell mussel more vulnerable to diarrhetic shellfish toxin-producing harmful algae - Kuan-Kuan Yuan; Ying-Ying Yu; Yan-Hang Mo; Yu-Jie Liu; Wei-Xia Zhang; Jin-Jin Lv; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Science of The Total Environment, 2024)

Novel fluorescence strategy based on G-quadruplex structure-switching aptamer for enrofloxacin detection in food and environmental samples - Gang Shen; Yingnan Ma; Hong Zhang; Fangfang Wang; Fengmin Yang; Huanfeng Ye; Runzhi Li; Changzheng Wang; Yalin Tang (Food Chemistry, 2024)

Preparation of novel gallic acid-based dummy-template molecularly imprinted polymer adsorbents for rapid adsorption of dibutyl phthalate from water - Shunying Li; Yuanhao Zhou; Qiangqiang Xu; Haoxiang Chen; Shengpeng Shi; Ruobing Jia; Yingying Zhang; Hong Ye (Environmental Pollution, 2024)

Recent advances in microplastic removal from drinking water by coagulation: Removal mechanisms and influencing factors - Yufeng Mao; Zuoyuan Hu; Hong Li; Huaili Zheng; Shengfa Yang; Weiwei Yu; Bingran Tang; Hao Yang; Ruixu He; Wenshu Guo; Kailai Ye; Aoguang Yang; et al. (Environmental Pollution, 2024)

Integration of the Metabolome and Transcriptome Reveals Diurnal Variability in the Effects of Melatonin on Salt Tolerance in Maize Seedlings - Jiajie Wang; Di Yan; Zhenzong Lu; Rui Liu; Yue Hong; Ye Wang; Zhen Peng; Chunxin Yu; Yuerong Gao; Ziyan Liu; Liusheng Duan; Runzhi Li (Journal of Plant Growth Regulation, 2024)

Characterizing spatiotemporal dynamics of carbon emissions in peri-urban residential communities: A life cycle perspective - Lishan Xiao; Weiyue Li; Leji Dong; Xian Wu; Hong Ye (Journal of Cleaner Production, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Distribution Characteristics, Source Analysis of Heavy Metal(oid)s, and Ecological and Health Risk Assessment around Shale Gas Extraction Platform in Sichuan, China - Bing Wang; Kefeng Li; Hong Ye; Chunyang Gao; Wenhui Jin; Guilin Xie (Water, Air, & Soil Pollution, 2024)

Meta-analysis of the SARS-CoV-2 positivity rate in municipal wastewater - Keyi Cheng; Ye Lv; Chaokang Li; Shi Cheng; Shanshan Xu; Xin Gao; Hong Xu (Environmental Geochemistry and Health, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Stochastic processes drive the diversity and composition of methanogenic community in a natural mangrove ecosystem - Xindi Li; Fei Ye; Hua Xiang; Yiguo Hong; Jiapeng Wu; Minshi Deng; Yu Wang (Marine Environmental Research, 2024)

A multifunctional interface optimization strategy for efficient Quasi-2D blue perovskite Light-Emitting diodes - Yuliang Ye; Zhou Cui; Zunxian Yang; Zhiwei Zeng; Zongyi Meng; Hongyi Hong; Songwei Ye; Zhiming Cheng; Qianting Lan; Jiaxiang Wang; Ye Chen; Hui Zhang; et al. (Chemical Engineering Journal, 2024)

Geochemistry of iron and trace metals in seep carbonates of the middle Okinawa Trough impacted by hydrothermal plumes - Shuang-Shuang Qin; Mao-Xu Zhu; Tie Li; Xilin Zhang; Cuiling Xu; Hong Cao; Wei Geng; Bin Zhai; Ye Chen; Shixing Li; Zhilei Sun (Chemical Geology, 2024)

Correction: Root Exudates Modulate Rhizosphere Microbial Communities during the Interaction of Pseudomonas chlororaphis, β-Aminobutyric Acid, and Botrytis Cinerea in Tomato Plants - Yu Zhao; Zhaoxia Jin; Ye Hong; Yahui Zhang; Zijie Lu; Yang Li (Journal of Plant Growth Regulation, 2024)

Root Exudates Modulate Rhizosphere Microbial Communities during the Interaction of Pseudomonas chlororaphis, β-Aminobutyric Acid, and Botrytis Cinerea in Tomato Plants - Yu Zhao; Zhaoxia Jin; Ye Hong; Yahui Zhang; Zijie Lu; Yang Li (Journal of Plant Growth Regulation, 2024)

Dissection and validation of quantitative trait loci (QTLs) conferring grain size and grain weight in rice - Ping Sun; Yuanyuan Zheng; Pingbo Li; Hong Ye; Hao Zhou; Guanjun Gao; Qinglu Zhang; Yuqing He (Euphytica, 2024)

2D/2D Bi2MoO6/CoAl LDH S-scheme heterojunction for enhanced removal of tetracycline: Performance, toxicity, and mechanism - Huiyin Ye; Yidan Luo; Shuohan Yu; Guangying Shi; Aofeng Zheng; Yong Huang; Mingshan Xue; Zuozhu Yin; Zhen Hong; Xibao Li; Xianchuan Xie; Bin Gao (Chemosphere, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Co-exposure of nanoplastics and arsenic causes neurotoxicity in zebrafish (Danio rerio) through disrupting homeostasis of microbiota–intestine–brain axis - Cheng Zhang; Yanyao Li; Haibo Yu; Tian Li; Limin Ye; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Integrated surrogate framework for reactive transport simulation of uranium in situ leaching with generative models - Wen-gui Ji; Yue Luo; Bing Wang; Xun Li; Jin-hui Liu; Yan-hong Zhang; Da-ye Liang (Journal of Hydrology, 2024)

Fe-Ni bimetallic adsorbent for efficient As2O3 removal from coal-fired flue gas under a wide temperature range: Experimental and DFT study - Xin Zhang; Bowen Zhang; Qilin Zhang; Jiang Wu; Lingyu Ye; Shuai Li; Yang Ling; Guangqian Luo; Hong Yao; Biao Wu (Fuel, 2024)

Paraprobiotic and postbiotic forms of Bacillus siamensis improved growth, immunity, liver and intestinal health in Lateolabrax maculatus fed soybean meal diet - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Sustainable paramylon production from food waste by Euglena gracilis using a waste-based cell immobilisation technique - Jin-Hua Mou; Si-Fen Liu; Li-Li Yang; Zi-Hao Qin; Yu-Feng Yang; Zhen-Yao Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Indole-3-carboxaldehyde ameliorates ionizing radiation-induced hematopoietic injury by enhancing hematopoietic stem and progenitor cell quiescence - Dongwei Guan; Yonghao Yang; Mao Pang; Xinlei Liu; Yang Li; Pengju Huang; Haitao Shang; Hong Wei; Zhijia Ye (Molecular and Cellular Biochemistry, 2024)

Aerobic methane production by phytoplankton as an important methane source of aquatic ecosystems: Reconsidering the global methane budget - Yufeng Mao; Tong Lin; Hong Li; Ruixu He; Kailai Ye; Weiwei Yu; Qiang He (Science of The Total Environment, 2024)

Characteristic chromanone acids from Calophyllum membranaceum: Determination of C-3 configuration and anti-inflammatory activity - Wei Shen; Lun Li; Qing-He Liu; Jia-Min Cui; Wei Shi; Xin-Hong Shi; Xiao-Qi Zhang; Wen-Cai Ye; Xiao-Long Hu; Hao Wang (Phytochemistry, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Synergistic effect between Ni single atoms and Ni nanoparticles for effectively boosting sustainable co-electrolysis of CO2 and hydrazine - Min Li; Ye Hu; Wenhui Fang; Shixian Xin; Ying Wu; Yutao Cao; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Geographical distribution and potential distribution prediction of thirteen species of Citrus L. in China - Zhenhai Huang; Zexi Li; Lewen Yao; Yanghe Yuan; Zhengyi Hong; Shiyuan Huang; Ying Wang; Jianhao Ye; Lanyue Zhang; Jinlong Ding (Environmental Science and Pollution Research, 2023)

Reusable and near-infrared light-activated Zinc(II) metalated porphyrin with synergetic PDT/PTT for eradicating bacterial pneumonia - Xiaozhuang Duan; Jie Li; Siyuan Huang; Anran Li; Yufei Zhang; Yun Xue; Xianhui Song; Ye Zhang; Shihao Hong; Huanhuan Gao; Zhongming Wu; Xinge Zhang (Chemical Engineering Journal, 2023)

Dietary nano-selenium improves health of liver and intestine of grass carp Ctenopharyngodon idella after overwintering - Limin Ye; Sha Liu; Xiaotian Zhang; Chi Wang; Pengju Li; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2023)

Development of SNP markers to identify the sex of the giant panda from naturally degraded fecal samples - Wei Xu; Daxing Xie; Jie Kou; Xiuyue Zhang; Yan Li; Ye Wang; Liang Zhang; Hong Liu; Jiawen Liu; Juan Wang; Li Luo; Xiaolan Wang; et al. (Conservation Genetics Resources, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Tailoring pore structures in poly(propylene-co-1-butene) membranes: Unlocking versatility for advanced applications - Xian Zhang; Cheng-Ye Zhu; Wangbei Cao; Zhao-Yu Ma; Hao-Nan Li; Hong-Qing Liang; Chuan-Jie Fang; Xiao-Jun Huang; Zhi-Kang Xu (Chemical Engineering Journal, 2023)

Enhanced lithium storage in pomegranate-like carbon via dual confinement of lithiophilic seeds and Li deposition - Tangchao Xie; Weibin Ye; Hong Xiao; Banghai Wang; Zhiling Liu; Pan Xu; Weitao Zheng; Jialang He; Hengji Zhu; Yijuan Li; Ming-Sheng Wang; Shaoming Huang (Chemical Engineering Journal, 2023)

Photocatalytic reactive distillation - A novel process intensification approach for purification of electronic-grade silicon tetrachloride - Xiong Zhao; Zhengkun Hou; Shuhu Guo; Renze Shi; Ye Wan; Jianhua Liu; Zhenjun Yuan; Hong Li; Dazhou Yan; Xin Gao (Chemical Engineering Journal, 2023)

Utilization of lipidic food waste as low-cost nutrients for enhancing the potentiality of biofuel production from engineered diatom under temperature variations - Yu-Feng Yang; Guang-Bin Ye; Hua-Jun Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiao-Fei Zheng; Arivalagan Pugazhendhi; Xiang Wang (Bioresource Technology, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

PoClu, a teleost Clusterin, acts as a negative regulator in complement activation and antibacterial immunity - Guan-yu Chen; Ji-xing Feng; Wen-kai Shi; Hong-ye Wang; Jian Zhang; Xue-peng Li (Aquaculture, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

A comprehensive evaluation of spontaneous pelvic organ prolapse in rhesus macaques as an ideal model for the study of human pelvic organ prolapse - Yaqian Li; Jian Liu; Ye Zhang; Meng Mao; Hong Wang; Yidi Ma; Zhigang Chen; Youyue Zhang; Chengmin Liao; Xiaoqing Chang; Qianqian Gao; Jianbin Guo; et al. (Science Bulletin, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Probiotic components of Bacillus siamensis LF4 mitigated β-conglycinin caused cell injury via modulating TLR2/MAPKs/NF-κB signaling in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Realgar-Induced Neurotoxicity: Crosstalk Between the Autophagic Flux and the p62-NRF2 Feedback Loop Mediates p62 Accumulation to Promote Apoptosis - Rui Feng; Jieyu Liu; Zhao Yang; Tiantian Yao; Ping Ye; Xiuhan Li; Jiaxin Zhang; Hong Jiang (Molecular Neurobiology, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

PxRdl2 dsRNA increased the insecticidal activities of GABAR-targeting compounds against Plutella xylostella - Ben-Jie Li; Kun-Kun Wang; Ye Yu; Jia-Qi Wei; Jian Zhu; Jia-Li Wang; Fei Lin; Han-Hong Xu (Pesticide Biochemistry and Physiology, 2023)

Seasonal dynamics of coastal pollution migration in open waters with intensive marine ranching - Zhixin Cheng; Guoqiang Hong; Qingbo Li; Shangheng Liu; Shuang Wang; Ye Ma (Marine Environmental Research, 2023)

High-energy and dendrite-free solid-state zinc metal battery enabled by a dual-network and water-confinement hydrogel electrolyte - Zhenglin Li; Guoqiang Zhou; Lei Ye; Jinyu He; Wangwang Xu; Shu Hong; Weimin Chen; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Chemical Engineering Journal, 2023)

Self-assembled synthesis of Pd/SPEn from polyelectrolyte membranes for efficient direct synthesis of H2O2 via inhibiting the dissociation of O − O bond - Entong Ye; Zheng Chen; Yongyong Shi; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Quansheng Wu; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

An arabinogalactan extracted with alkali from Portulaca oleracea L. used as an immunopotentiator and a vaccine carrier in its conjugate to BSA - Ye Yang; Hong Li; Feihe Wang; Peng Jiang; Guiyun Wang (Carbohydrate Polymers, 2023)

Toxicity and potential underlying mechanism of Karenia selliformis to the fish Oryzias melastigma - Qin-yuan Liu; Zi-min Chen; Da-wei Li; Ai-feng Li; Ying Ji; Hong-ye Li; Wei-dong Yang (Aquatic Toxicology, 2023)

Acer truncatum leaves reduce lipid accumulation and improve liver and intestine health of grass carp (Ctenopharyngodon idella) fed with high-fat diet - Limin Ye; Xiaotian Zhang; Chi Wang; Sha Liu; Pengju Li; Cheng Zhang; Qinfeng Gao; Hong Ji; Haibo Yu (Aquaculture, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Nanographite-assisted matrix solid phase dispersion microextraction of active and toxic compounds from complex food matrices using cyclodextrin aqueous solution as elution solvent - Si-Chen Zhu; Ying Shi; Huang-Fei Jin; Jun Cao; Li-Hong Ye (Food Chemistry, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Climate and geochemistry at different altitudes influence soil fungal community aggregation patterns in alpine grasslands - Jia Li; Xia Wang; Jin Hong Wu; Yu Xin Sun; Yuan Ye Zhang; Yun Fei Zhao; Zheng Huang; Wen Hui Duan (Science of The Total Environment, 2023)

Application of the global stability index method to shelf-life prediction and physiochemical characteristics analysis of enteral feeding formula during storage - Hong Yang; Li Li Xu; Ling Hou; Tong Cheng Xu; Shu Hong Ye (Journal of Food Engineering, 2023)

Systematic exploration of transcriptional responses of interspecies interaction between Karenia mikimotoi and Prorocentrum shikokuense - Jian-Wei Zheng; Guo-Hui He; Rui-Xia Xu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Methane distribution and sea-to-air methane flux in the Dongsha area of the South China Sea - Cuiling Xu; Zhilei Sun; Qing Li; Xianrong Zhang; Xilin Zhang; Bin Zhai; Qiang Fu; Yuhai Sun; Wei Geng; Hong Cao; Ye Chen; Nengyou Wu (Continental Shelf Research, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

Fe and Mo dual-site single-atom catalysts for high-efficiency wide-pH hydrogen evolution and alkaline overall water splitting - Wenhui Fang; Ying Wu; Shixian Xin; Ye Hu; Jiaqi Dang; Min Li; Bozhen Chen; Hong Zhao; Zengxi Li (Chemical Engineering Journal, 2023)

Identification of 14 glutathione S-transferase genes from Lasioderma serricorne and characterization of LsGSTe1 involved in lambda-cyhalothrin detoxification - Xi-Ya Liu; Hui-Mei Sun; Yi-Hong Luo; Mao-Ye Li; Hai-Bing Liu; Su Liu (Pesticide Biochemistry and Physiology, 2023)

Mariculture affects antibiotic resistome and microbiome in the coastal environment - Lu-Xi He; Liang-Ying He; Fang-Zhou Gao; Min Zhang; Jun Chen; Wei-Li Jia; Pu Ye; Yu-Wei Jia; Bai Hong; Si-Si Liu; You-Sheng Liu; Jian-Liang Zhao; et al. (Journal of Hazardous Materials, 2023)

Commensal Bacillus siamensis LF4 ameliorates β-conglycinin induced inflammation in intestinal epithelial cells of Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Xi-Yue Ding; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Cytochrome P450-mediated co-metabolism of fluoroquinolones by Haematococcus lacustris for simultaneously promoting astaxanthin and lipid accumulation - Xiang Wang; Zhong-Hong Zhang; Kuan-Kuan Yuan; Hui-Ying Xu; Guo-Hui He; Libin Yang; Joseph Buhagiar; Wei-Dong Yang; Yalei Zhang; Carol Sze Ki Lin; Hong-Ye Li (Chemical Engineering Journal, 2023)

Precisely mapping a major QTL for grain weight on chromosome 5B of the founder parent Chuanmai42 in the wheat-growing region of southwestern China - Meijin Ye; Hongshen Wan; Wuyun Yang; Zehou Liu; Qin Wang; Ning Yang; Hai Long; Guangbing Deng; Yumin Yang; Hong Feng; Yonghong Zhou; Cairong Yang; et al. (Theoretical and Applied Genetics, 2023)

Interaction between STK33 and autophagy promoted renal cell carcinoma metastasis by regulating mTOR/ULK1 signaling pathway - Xiaomei Li; Min Lin; Min Liu; Hong Ye; Shuming Qin (Molecular Biology Reports, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

To promote catalytic ozonation of toluene by tuning Brönsted acid sites via introducing alkali metals into the OMS-2-SO42-/ZSM-5 catalyst - Wei Hong; Yan Liu; Xinxin Jiang; Chenguang An; Tianle Zhu; Ye Sun; Haining Wang; Fangxia Shen; Xiang Li (Journal of Hazardous Materials, 2023)

Triclocarban triggers osteoarthritis via DNMT1-mediated epigenetic modification and suppression of COL2A in cartilage tissues - Yibo Zhang; Liu He; Yiqi Yang; Jieqiong Cao; Zijian Su; Bihui Zhang; Huiying Guo; Zhenyu Wang; Peiguang Zhang; Junye Xie; Jieruo Li; Jinshao Ye; et al. (Journal of Hazardous Materials, 2023)

Environmental profiling microalgae-based eicosapentaenoic acid production along the technical advancement via life cycle assessment - Zi-Hao Qin; Xiaomeng Hu; Jin-Hua Mou; Guo-Hui He; Guang-Bin Ye; Hong-Ye Li; Shauhrat Singh Chopra; Liang Dong; Carol Sze Ki Lin; Xiang Wang (Journal of Cleaner Production, 2023)

Triphenylamine-based covalent triazine framework @ carbon nanotube complex: efficient photogenerated charges migration for metal free photocatalytic Cr(VI) reduction - Xiahong Xu; Wei Huang; Xiaodan Li; Yan Sui; Wentong Chen; Yuntong Li; Huixian Ye; Changwang Pan; Hong Zhong; Meicheng Wen (Journal of Environmental Chemical Engineering, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Ioversol Induced Microglia Proinflammatory Activation and Oxidative Stress in Rats - Tao Li; Lili Zhao; Hong Fan; Zhiyang Chen; Ye Li; Meijuan Dang; Ziwei Lu; Jialiang Lu; Qiao Huang; Heying Wang; Shengxi Wu; Guilian Zhang; et al. (Neurotoxicity Research, 2023)

Nanoplastics promote arsenic-induced ROS accumulation, mitochondrial damage and disturbances in neurotransmitter metabolism of zebrafish (Danio rerio) - Cheng Zhang; Yanyao Li; Haibo Yu; Limin Ye; Tian Li; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2023)

Microcystin-LR exposure interfered maintenance of colonic microenvironmental homeostasis in rat - Yang Liu; Chun-Li Qi; Da-Wei Li; Hong-Ye Li; Rui-Man Li; Wei-Dong Yang (Food and Chemical Toxicology, 2023)

Recent advances in application of heterogeneous electro-Fenton catalysts for degrading organic contaminants in water - Wenjing Chen; Danlian Huang; Cui Lai; Yukui Fu; Wenfang Chen; Haoyang Ye; Huan Yi; Bisheng Li; Ling Li; Fanzhi Qin; Hong Qin; Lei Qin (Environmental Science and Pollution Research, 2023)

Adsorption removal of styrene on C–Cl grafted silica gel adsorbents - Shiyu Hou; Zheng-Hong Huang; Tianle Zhu; Yiliang Tang; Ye Sun; Xiang Li; Fangxia Shen (Chemosphere, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

A water-gating and zinc-sieving lignocellulose nanofiber separator for dendrite-free rechargeable aqueous zinc ion battery - Zhenglin Li; Lei Ye; Guoqiang Zhou; Wangwang Xu; Kangning Zhao; Xiaoman Zhang; Shu Hong; Tongtong Ma; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Chemical Engineering Journal, 2023)

Draft genome of the medicinal tea tree Melaleuca alternifolia - Xiaoning Zhang; Silin Chen; Ye Zhang; Yufei Xiao; Yufeng Qin; Qing Li; Li Liu; Buming Liu; Ling Chai; Hong Yang; Hailong Liu (Molecular Biology Reports, 2023)

Portal vein tumor thrombosis in hepatocellular carcinoma: molecular mechanism and therapy - Xing-Hao Zhou; Jing-Ru Li; Tang-Hui Zheng; Hong Chen; Chen Cai; Sheng-Long Ye; Bo Gao; Tong-Chun Xue (Clinical & Experimental Metastasis, 2023)

Atopomonas sediminilitoris sp. nov., isolated from beach sediment of Zhairuo Island, China - Kejing Li; Zhenbo Ye; Gen Chen; Kaiwen Zheng; Jun Yin; Sanjit Chandra Debnath; Cen Yan; Yi Hong; Zhen Guo; Pinmei Wang; Fabai Wu; Daoqiong Zheng (Antonie van Leeuwenhoek, 2023)

Geographical distribution and predict potential distribution of Angelica L. genus - Zekai Tan; Yanghe Yuan; Shiyuan Huang; Yingxin Ma; Zhengyi Hong; Ying Wang; Xianyi Wu; Zexi Li; Jianhao Ye; Lanyue Zhang (Environmental Science and Pollution Research, 2023)

Reducing food-system nitrogen input and emission through circular agriculture in montane and coastal regions - Li Xing; Tao Lin; Yuanchao Hu; Meixia Lin; Yuqin Liu; Guoqin Zhang; Hong Ye; Xiongzhi Xue (Resources, Conservation and Recycling, 2023)

Construction of an unmarked genetically engineered strain Bacillus subtilis WB800-ipaH capable of degrading iprodione and its pilot application - Mingliang Zhang; Qian Li; Xuekun Bai; Siyuan Gao; Qian Zhu; Bin Ye; Yidong Zhou; Jiguo Qiu; Xin Yan; Qing Hong (International Biodeterioration & Biodegradation, 2023)

Rapid identification of fish species by laser-induced breakdown spectroscopy and Raman spectroscopy coupled with machine learning methods - Lihui Ren; Ye Tian; Xiaoying Yang; Qi Wang; Leshan Wang; Xin Geng; Kaiqiang Wang; Zengfeng Du; Ying Li; Hong Lin (Food Chemistry, 2023)

Perfluorodecanoic acid promotes adipogenesis via NLRP3 inflammasome-mediated pathway in HepG2 and 3T3-L1 cells - Taotao Wang; Hong Xu; Yu Guo; Zhanming Li; Hua Ye; Liang Wu; Yuanxin Guo; Dongxu Wang (Food and Chemical Toxicology, 2023)

Coupled carbon structure and iron species for multiple periodate-based oxidation reaction - Ling Xiang; Eydhah Almatrafi; Hailan Yang; Haoyang Ye; Fanzhi Qin; Huan Yi; Yukui Fu; Xiuqin Huo; Wu Xia; Hong Li; Ming Yan; Chengyun Zhou; et al. (Chemical Engineering Journal, 2023)

High performance carbon dioxide electroreduction in ionic liquids with in situ shell-isolated nanoparticle-enhanced Raman spectroscopy - Ye Hu; Zhongdong Gan; Shixian Xin; Wenhui Fang; Min Li; Yanlei Wang; Wei Cui; Hong Zhao; Zengxi Li; Xiangping Zhang (Chemical Engineering Journal, 2023)

Responses of ABCB and ABCC transporters to the toxic dinoflagellate Prorocentrum lima in the mussel Perna viridis - Jin-Jin Lv; Kuan-Kuan Yuan; Guan-Xiu Lu; Hong-Ye Li; Hang Fai Kwok; Wei-dong Yang (Aquatic Toxicology, 2023)

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

Within-day variation and health risk assessment of trihalomethanes (THMs) in a chlorinated indoor swimming pool in China - Xianyun Zheng; Jingchao Xu; Ye Gao; Wanghong Li; Yimei Chen; Hong Geng; Jianwei Yue; Min Xu (Environmental Science and Pollution Research, 2022)

Astrocyte Activation, but not Microglia, Is Associated with the Experimental Mouse Model of Schizophrenia Induced by Chronic Ketamine - Ying Wei; Li Xiao; Weihao Fan; Jing Zou; Hong Yang; Bo Liu; Yi Ye; Di Wen; Linchuan Liao (Journal of Molecular Neuroscience, 2022)

Comprehensive profiling of phytochemicals in the fruits of Gardenia jasminoides Ellis and its variety using liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry - Xiao Ye; Xiao-Qian Liu; Dong Zhang; Wei-Hong Feng; Yao-Hua Liang; Chun Li; Zhi-Min Wang (Journal of Natural Medicines, 2022)

Molecular detection of spotted fever group rickettsiae in hedgehogs (Erinaceus amurensis) and hedgehog-attached ticks in Xuyi County, Southeast China - Changqiang Zhu; Lele Ai; Yong Qi; Yunsheng Liu; Hong Li; Fuqiang Ye; Qiuwei Wang; Yizhe Luo; Weilong Tan; Chunmeng Shi (Experimental and Applied Acarology, 2022)
Tick-borne diseases like Rickettsia , Anaplasma and Ehrlichia are widespread infectious zoonoses that threaten the health of both humans and animals worldwide. Ticks and their hosts, such as hedgehogs, can play a crucial role in transmitting tick-borne diseases and the cycle of Rickettsia . To investigate the presence and identity of Rickettsia in hedgehogs and hedgehog-attached ticks in Xuyi County, Southeast China, 114 ticks were collected from 45 hedgehogs captured totally. Via morphological and molecular methods, all these ticks were identified as two species: Haemaphysalis flava (110/114, 96.5%) and Haemaphysalis longicornis (4/114, 3.5%). Rickettsia spp. were genotypically characterized by PCR targeting rrs , gltA , ompA , ompB , and sca4 gene fragments. The prevalence of spotted fever group rickettsiae (SFGR) infection found in hedgehogs and ticks was 17.8% (8/45) and 78.1% (89/114), respectively. Phylogenetic analyses demonstrated that those Rickettsia spp. belong to two species: Rickettsia heilongjiangensis ( R. heilongjiangensis XY-1) and a potential new species, Candidatus Rickettsia xuyiensis XY-2. The present study gave the first evidence of R. heilongjiangensis and Candidatus R. xuyiensis in ticks and hedgehogs of Southeast China. Our findings suggest that hedgehogs might be involved in the natural transmission cycle of Rickettsia species.

Formation and evolution of secondary particulate matter during heavy haze pollution episodes in winter in a severe cold climate region of Northeast China - Ye Hong; Junying Sun; Yanjun Ma; Yangfeng Wang; Xiaolan Li; Yunhai Zhang; Ningwei Liu; Deping Zhou (Environmental Science and Pollution Research, 2022)

Three new sesquiterpenoid alkaloids from the roots of Tripterygium wilfordii and its cytotoxicity - Hong Liang Ye; Yan Liu; Juan Pan; Wei Guan; Yuan Liu; Xiao Mao Li; Si Yi Wang; Adnan Mohammed Algradi; Bing You Yang; Hai Xue Kuang (Natural Product Research, 2022)

Transport of phosphorus in runoff and sediment with surface runoff from bare purple soil during indoor simulated rainfall - Xiao Ma; Jie Yang; Xiang-jun Zhou; Hong-tao Wu; Qiao Xiong; Ye Li (Journal of Mountain Science, 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Ligustilide ameliorates cognitive impairment via AMPK/SIRT1 pathway in vascular dementia rat - Dong Peng; Han-Zi Qiao; Hong-Yu Tan; Yi-Xue Wang; Dan Luo; Li-Jun Qiao; Ye-Feng Cai; Shi-Jie Zhang; Qi Wang; Li Guan (Metabolic Brain Disease, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Schwann-like cell conditioned medium promotes angiogenesis and nerve regeneration - Jiahong Yu; Kai Ye; Jing Li; Yusheng Wei; Jiqin Zhou; Wei Ni; Lei Zhang; Tianyan Chen; Bin Tang; Hong Xu; Jiabo Hu (Cell and Tissue Banking, 2022)

Multi-omics analysis reveals metabolism of okadaic acid in gut lumen of rat - Yang Liu; Yang Lu; Yu-Hu Jiao; Da-Wei Li; Hong-Ye Li; Wei-Dong Yang (Archives of Toxicology, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

The influences of α-hemolytic Streptococcus on class switching and complement activation of human tonsillar cells in IgA nephropathy - Muyao Ye; Chang Wang; Ling Li; Qiulan Zhao; Youming Peng; Hong Liu (Immunologic Research, 2022)

Delayed body development with reduced triglycerides levels in leptin transgenic pigs - Yubo Qing; Muhammad Ameen Jamal; Dejia Shi; Sumei Zhao; Kaixiang Xu; Deling Jiao; Heng Zhao; Honghui Li; Baoyu Jia; Haizhen Wang; Hong-Ye Zhao; Hong-Jiang Wei (Transgenic Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Pivotal role of the gut microbiota in congenital insensitivity to pain with anhidrosis - Mi Zhang; Yishun Hong; Wenyao Wu; Ningbo Li; Baowen Liu; Jiaoli Sun; Xueqin Cao; Ting Ye; Ling Zhou; Cunming Liu; Chun Yang; Xianwei Zhang (Psychopharmacology, 2021)

Shifts in the Abundance and Community Composition of Particle-Associated and Free-Living Nitrospira Across Physicochemical Gradients in the Pearl River Estuary - Yiguo Hong; Jiapeng Wu; Lijing Jiao; Yaohao Hu; Fei Ye; Yu Wang; Yiben Li; Limei Wang; Aimin Long (Estuaries and Coasts, 2021)

The conversion of the nutrient condition alter the phenol degradation pathway by Rhodococcus biphenylivorans B403: A comparative transcriptomic and proteomic approach - Xiaohang Xie; Jiashu Liu; Zhengbing Jiang; Huanan Li; Meng Ye; Hong Pan; Jingwei Zhu; Huiting Song (Environmental Science and Pollution Research, 2021)

Spatial variability pattern of the anaerobic ammonia-oxidizing bacterial community across a salinity gradient from river to ocean - Yiben Li; Yiguo Hong; Jiapeng Wu; Yu Wang; Fei Ye (Ecotoxicology, 2021)

Modulation of the 5-HT 3 A receptor current by desacylbaldrinal - Li-Xia Wang; Hu-Lan Chen; Hong-Ling Yan; Fei Tang; Hai Zhang; Hong-Xiang Li; Qiang Ye; Cheng Peng; Yu-Zhu Tan (Natural Product Research, 2021)

TREM-1 Exacerbates Neuroinflammatory Injury via NLRP3 Inflammasome-Mediated Pyroptosis in Experimental Subarachnoid Hemorrhage - Pengfei Xu; Ye Hong; Yi Xie; Kang Yuan; Juanji Li; Rui Sun; Xiaohao Zhang; Xiaolei Shi; Rongrong Li; Jiaonan Wu; Xinfeng Liu; Wei Hu; et al. (Translational Stroke Research, 2021)

Psychological and occupational impact on healthcare workers and its associated factors during the COVID-19 outbreak in China - Xiaodan Zhang; Ye Jiang; Hu Yu; Yafen Jiang; Qiongfeng Guan; Weihe Zhao; Yingying Mao; Danfeng Huang; Wenke Hong; Da Li (International Archives of Occupational and Environmental Health, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Preliminary report on the improved resistance towards Pseudomonas syringae pv. actinidiae of cultivated kiwifruit (Actinidia chinensis) when grafted onto wild Actinidia guilinensis rootstock in vitro - Fa-ming Wang; Jie-wei Li; Kai-yu Ye; Hong-juan Gong; Ping-ping Liu; Qiao-sheng Jiang; Bei-bei Qi; Quan-hui Mo (Journal of Plant Pathology, 2021)

Complete genome analysis of a novel iflavirus from a leaf beetle, Aulacophora lewisii - Zhuang-Xin Ye; Yue-Hong Li; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Genetic diversity of Prorocentrum donghaiense population during bloom in the East China Sea revealed by microsatellite - Hong-jia Huang; Chu-qiao Gan; Shao-wen Xiao; Cheng Zou; Srinivasan Balamurugan; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2020)

Improved production of GTKO/hCD55/hCD59 triple-gene-modified Diannan miniature pigs for xenotransplantation by recloning - Heng Zhao; Yuying Li; Thanapa Wiriyahdamrong; Zaimei Yuan; Yubo Qing; Honghui Li; Kaixiang Xu; Jianxiong Guo; Baoyu Jia; Xuezeng Zhang; Wenmin Cheng; Yanhua Su; et al. (Transgenic Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Gypenosides Prevent H2O2-Induced Retinal Ganglion Cell Apoptosis by Concurrently Suppressing the Neuronal Oxidative Stress and Inflammatory Response - Hong-Kan Zhang; Yuan Ye; Kai-Jun Li; Zhen-ni Zhao; Jian-Feng He (Journal of Molecular Neuroscience, 2020)
Our previous study demonstrated that gypenosides (Gp) exert protective effects on retinal nerve fibers and axons in a mouse model of experimental autoimmune optic neuritis. However, the therapeutic mechanisms remain unclear. Thus, in this study, a model of oxidative damage in retinal ganglion cells (RGCs) was established to investigate the protective effect of Gp, and its possible influence on oxidative stress in RGCs. Treatment of cells with H 2 O 2 induced RGC injury owing to the generation of intracellular reactive oxygen species (ROS). In addition, the activities of antioxidative enzymes decreased and the expression of inflammatory factors increased, resulting in an increase in cellular apoptosis. Gp helped RGCs to become resistant to oxidation damage by directly reducing the amount of ROS in cells and exerting protective effects against H 2 O 2 -induced apoptosis. Treatment with Gp also reduced the generation of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), and increased nuclear respiratory factor 2 (Nrf-2) levels so as to increase the levels of heme oxygenase-1 (HO-1) and glutathione peroxidase 1/2 (Gpx1/2), which can enhance antioxidation in RGCs. In conclusion, our data indicate that neuroprotection by Gp involves its antioxidation and anti-inflammation effects. Gp prevents apoptosis through a mitochondrial apoptotic pathway. This finding might provide novel insights into understanding the mechanism of the neuroprotective effects of gypenosides in the treatment of optic neuritis.

Plastidial and ER Triacylglycerol Biosynthesis in a Growth Phase-Dependent Manner in the Heterokont Nannochloropsis oceanica - Dan Huang; Da-Wei Li; Srinivasan Balamurugan; Jian-Wei Zheng; Wan-Jun Liu; Li-Gong Zou; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Frontiers in Marine Science, 2020)

Chemical Stimulation of Renal Tissue Induces Sympathetic Activation and a Pressor Response via the Paraventricular Nucleus in Rats - Chao Ye; Yun Qiu; Feng Zhang; Ai-Dong Chen; Hong Zhou; Jue-Jin Wang; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Neuroscience Bulletin, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Photoproduction of nitric oxide in seawater - Ye Tian; Gui-Peng Yang; Chun-Ying Liu; Pei-Feng Li; Hong-Tao Chen; Hermann W. Bange (Ocean Science, 2020)
Nitric oxide (NO) is a short-lived intermediate of the oceanic nitrogen cycle. However, our knowledge about its production and consumption pathways in oceanic environments is rudimentary. In order to decipher the major factors affecting NO photochemical production, we irradiated several artificial seawater samples as well as 31 natural surface seawater samples in laboratory experiments. The seawater samples were collected during a cruise to the western tropical North Pacific Ocean (WTNP, a N–S section from 36 to 2∘ N along 146 to 143∘ E with 6 and 12 stations, respectively, and a W–E section from 137 to 161∘ E along the Equator with 13 stations) from November 2015 to January 2016. NO photoproduction rates from dissolved nitrite in artificial seawater showed increasing trends with decreasing pH, increasing temperature, and increasing salinity. In contrast, NO photoproduction rates (average: 0.5±0.2×10-12 mol L−1 s−1) in the natural seawater samples from the WTNP did not show any correlations with pH, water temperature, salinity, or dissolved inorganic nitrite concentrations. The flux induced by NO photoproduction in the WTNP (average: 13×10-12 mol m−2 s−1) was significantly larger than the NO air–sea flux density (average: 1.8×10-12 mol m−2 s−1), indicating a further NO loss process in the surface layer.

One-step generation of zebrafish carrying a conditional knockout-knockin visible switch via CRISPR/Cas9-mediated intron targeting - Jia Li; Hong-Yu Li; Shan-Ye Gu; Hua-Xing Zi; Lai Jiang; Jiu-Lin Du (Science China Life Sciences, 2020)

Optimizing the wavefield storage strategy in reflection-acoustic logging reverse-time migration - Yu-Sheng Li; Ning Li; Ye Yuan; Hong-Liang Wu; Zhou Feng; Peng Liu (Applied Geophysics, 2019)

Harnessing the Lipogenic Potential of Δ6-Desaturase for Simultaneous Hyperaccumulation of Lipids and Polyunsaturated Fatty Acids in Nannochloropsis oceanica - Fan Yang; Wasiqi Yuan; Yuhan Ma; Srinivasan Balamurugan; Hong-Ye Li; Songling Fu; Lifang Wu (Frontiers in Marine Science, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Assessing the influence of the minimum measured diameter on forest spatial patterns and nearest neighborhood relationships - Yuan-fa Li; Hai-peng Yang; Hong-xiang Wang; Shao-ming Ye; Wen-zhen Liu (Journal of Mountain Science, 2019)

Exploring the Potential of Mesoporous Silica as a Carrier for Puerarin: Characterization, Physical Stability, and In Vivo Pharmacokinetics - Zhi Wang; Bei-Ni Ye; Yong-Tai Zhang; Jian-Xu Xie; Wan-Si Li; Hong-Tao Zhang; Ying Liu; Nian-Ping Feng (AAPS PharmSciTech, 2019)

Comprehensive genetic diagnosis of patients with Duchenne/Becker muscular dystrophy (DMD/BMD) and pathogenicity analysis of splice site variants in the DMD gene - Yan-mei Yang; Kai Yan; Bei Liu; Min Chen; Li-ya Wang; Ying-zhi Huang; Ye-qing Qian; Yi-xi Sun; Hong-ge Li; Min-yue Dong (Journal of Zhejiang University-SCIENCE B, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

Phosphate adsorption from wastewater using ZnAl-LDO-loaded modified banana straw biochar - Yan-Hong Jiang; An-Yu Li; Hua Deng; Cheng-Hui Ye; Yi Li (Environmental Science and Pollution Research, 2019)

A Spatial Ecology Study of Keshan Disease and Hair Selenium - Xiao Zhang; Tong Wang; Shie Li; Chao Ye; Jie Hou; Qi Li; Hong Liang; Huihui Zhou; Zhongying Guo; Xiaomin Han; Zhe Wang; Huan Wu; et al. (Biological Trace Element Research, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Broccoli Plants Over-expressing an ERF Transcription Factor Gene BoERF1 Facilitates Both Salt Stress and Sclerotinia Stem Rot Resistance - Ming Jiang; Zi-hong Ye; Hui-juan Zhang; Li-xiang Miao (Journal of Plant Growth Regulation, 2019)

Water-soluble ion components of PM10 during the winter-spring season in a typical polluted city in Northeast China - Ye Hong; Yanjun Ma; Junying Sun; Chaoliu Li; Yunhai Zhang; Xiaolan Li; Deping Zhou; Yangfeng Wang; Ningwei Liu (Environmental Science and Pollution Research, 2019)

Influence of rock fractures on the amplitude of dipole-source reflected shear wave - Hao Wang; Ning Li; Cai-Zhi Wang; Hong-Liang Wu; Peng Liu; Yu-Sheng Li; Ying-Ming Liu; Ye Yuan (Applied Geophysics, 2019)

Enrichment assessment of Sb and trace metals in sediments with significant variability of background concentration in detailed scale - Lingchen Mao; Hua Ye; Feipeng Li; Meng Yang; Hong Tao; Haifeng Wen (Environmental Science and Pollution Research, 2019)

Sesquiterpenes and lignans from the flower buds of Daphne genkwa and their nitric oxide inhibitory activities - Chun-Yang Zhang; Lan Luo; Jing Xia; Ya-Nan Song; Li-Jun Zhang; Miao Zhang; Khalid Rahman; Yin Ye; Hong Zhang; Jian-Yong Zhu (Natural Product Research, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Constitutive and Chloroplast Targeted Expression of Acetyl-CoA Carboxylase in Oleaginous Microalgae Elevates Fatty Acid Biosynthesis - Da-Wei Li; Wei-Hong Xie; Ting-Bin Hao; Jia-Xi Cai; Tian-Bao Zhou; Srinivasan Balamurugan; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Marine Biotechnology, 2018)

Anxiolytic-like effects of paeoniflorin in an animal model of post traumatic stress disorder - Zhi-Kun Qiu; Jia-Li He; Xu Liu; Jia Zeng; Wei Xiao; Qing-Hong Fan; Xiao-Meng Chai; Wei-Hai Ye; Ji-Sheng Chen (Metabolic Brain Disease, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Sevoflurane Affects Oxidative Stress and Alters Apoptosis Status in Children and Cultured Neural Stem Cells - Xue Zhou; Dihan Lu; Wen-da Li; Xiao-hui Chen; Xiao-yu Yang; Xi Chen; Zhi-bin Zhou; Jiang-Hong Ye; Xia Feng (Neurotoxicity Research, 2018)

Early diagnosis of acute kidney injury in aged patients undergoing percutaneous coronary intervention - Hong-hua Ye; Gen Shen; Qun Luo; Fang-fang Zhou; Xiao-ling Xie; Chun-yan Wang; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Predictive modeling of microbial single cells: A review - Tian Ding; Xin-Yu Liao; Qing-Li Dong; Xiao-Ting Xuan; Shi-Guo Chen; Xing-Qian Ye; Dong-Hong Liu (Critical Reviews in Food Science and Nutrition, 2018)

Effect of dietary astaxanthin on the growth performance, non-specific immunity, and antioxidant capacity of pufferfish (Takifugu obscurus) under high temperature stress - Chang-Hong Cheng; Zhi-Xun Guo; Chao-Xia Ye; An-Li Wang (Fish Physiology and Biochemistry, 2018)

Estimation of the daily soil/dust (SD) ingestion rate of children from Gansu Province, China via hand-to-mouth contact using tracer elements - Jin Ma; Li-bo Pan; Qin Wang; Chun-ye Lin; Xiao-li Duan; Hong Hou (Environmental Geochemistry and Health, 2018)

Indinavir Alters the Pharmacokinetics of Lamivudine Partially via Inhibition of Multidrug and Toxin Extrusion Protein 1 (MATE1) - Qing Li; Zhi Ye; Peng Zhu; Dong Guo; Hong Yang; Jin Huang; Wei Zhang; James E. Polli; Yan Shu (Pharmaceutical Research, 2018)

Activation of PXR inhibits LPS-induced NF-κB activation by increasing IκBα expression in HepG2 cells - Nanhui Ye; Hang Wang; Qiaoling Li; Chaotong Lin; Huahua Feng; Suying Lin; Jing Hong; Chun Meng (Molecular & Cellular Toxicology, 2018)

Inducible ATF3–NFAT axis aggravates podocyte injury - Hong Zhang; Shun Liang; Yue Du; Ruizhao Li; Chaosheng He; Wenjian Wang; Shuangxin Liu; Zhiming Ye; Xinling Liang; Wei Shi; Bin Zhang (Journal of Molecular Medicine, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

Phylogenetic and genetic characterization of a 2017 clinical isolate of H7N9 virus in Guangzhou, China during the fifth epidemic wave - Yongqiang Deng; Chunlin Li; Jianfeng Han; Yingfen Wen; Jian Wang; Wenxing Hong; Xiaofeng Li; Zhongyu Liu; Qing Ye; Jing Li; Changshuai Zhou; Lei Yu; et al. (Science China Life Sciences, 2017)

Identification of a putative seipin ortholog involved in lipid accumulation in marine microalga Phaeodactylum tricornutum - Yang Lu; Xiang Wang; Srinivasan Balamurugan; Wei-Dong Yang; Jie-Sheng Liu; Hong-Po Dong; Hong-Ye Li (Journal of Applied Phycology, 2017)

Silymarin inhibits adipogenesis in the adipocytes in grass carp Ctenopharyngodon idellus in vitro and in vivo - Peizhen Xiao; Zhou Yang; Jian Sun; Jingjing Tian; Zhiguang Chang; Xuexian Li; Baotong Zhang; Yuantu Ye; Hong Ji; Ermeng Yu; Jun Xie (Fish Physiology and Biochemistry, 2017)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Evaluating the relationship between spatial heterogeneity and temporal variability of larval fish assemblages in a coastal marine ecosystem (Haizhou Bay, China) - Zengguang Li; Zhenjiang Ye; Rong Wan; Yong Chen; Yongjun Tian; Yiping Ren; Hong Liu; Haisheng Hu; Robert Boenish (Marine Ecology, 2017)
In coastal marine ecosystems, spatial patterns of larval fish assemblages ( LFA s) tend to exhibit geographic stability because of relatively stable spawning site selection and predictable oceanographic phenomena such as eddies. To evaluate the relationship between spatial heterogeneity and temporal variability of LFA s, we conducted a high spatiotemporal resolution ichthyoplankton survey from April to July in 2013 in the shallow waters ( LFA s, likely owing to temperature effects of species composition and spawning period selection of adult fish, along with known temperature‐dependent survival rates of larval fish. Study of LFA spatiotemporal dynamics is essential for improved understanding of adult fish spawning behavior, and has potential to inform design and implementation of conservation and management measures (e.g. marine protected areas) in coastal systems.

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Low Serum Levels of Brain-Derived Neurotrophic Factor Were Associated with Poor Short-Term Functional Outcome and Mortality in Acute Ischemic Stroke - Jing Wang; Li Gao; Yan-Long Yang; Yu-Qian Li; Tao Chang; Ming-Hao Man; Xing-Ye Zhang; Shao-Chun Guo; Li-Hong Li (Molecular Neurobiology, 2017)

Identification of novel ATP7A mutations and prenatal diagnosis in Chinese patients with Menkes disease - Binbin Cao; Xiaoping Yang; Yinyin Chen; Qionghui Huang; Ye Wu; Qiang Gu; Jiangxi Xiao; Huixia Yang; Hong Pan; Junya Chen; Yu Sun; Li Ren; et al. (Metabolic Brain Disease, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Modern greenhouse culture of juvenile soft-shelled turtle, Pelodiscus sinensis - Jing Zhang; Fen Wang; Ye-Lin Jiang; Guan-Jun Hou; Yun-Sheng Cheng; Hong-Lian Chen; Xiang Li (Aquaculture International, 2017)

Life cycle environmental assessment of industrial hazardous waste incineration and landfilling in China - Jinglan Hong; Xiaofei Han; Yilu Chen; Meng Wang; Liping Ye; Congcong Qi; Xiangzhi Li (The International Journal of Life Cycle Assessment, 2017)

Characterization and expression analysis of a chalcone isomerase-like gene in relation to petal color of Actinidia chrysantha - Miaoxian Yang; Jiating Li; Chanjuan Ye; Hong Liang (Biologia, 2017)

High genetic diversity and absence of phylogeographic structure in breeding populations of vulnerable Saundersilarus saundersi (Charadriiformes: Laridae) in Bohai Bay, China - Ya-Nan Zhang; Bo-Ye Liu; Lu Dong; Hong-Xing Jiang; Xuan Wang; Xue-Min Wang; Chang-Zhan Song; Xiu-Ming Li; Shu-Hong Li (Conservation Genetics, 2017)

A Comprehensive Meta-analysis of Genetic Associations Between Key Polymorphic Loci in DNA Repair Genes and Glioma Risk - Ling Qi; Hong-quan Yu; Yu Zhang; Li-juan Ding; Dong-hai Zhao; Peng Lv; Wei-yao Wang; Ye Xu (Molecular Neurobiology, 2017)

Use of random forests and support vector machines to improve annual egg production estimation - Zengguang Li; Rong Wan; Zhenjiang Ye; Yong Chen; Yiping Ren; Hong Liu; Yiqian Jiang (Fisheries Science, 2017)

Hydrogen Sulfide Promotes Wheat Grain Germination Under Cadmium Stress - Zhong-Qin Huang; Shao-Can Ye; Lan-Ying Hu; Kang-Di Hu; Hong Yan; Wan-Jie Li; Hao Jiao; Hua Zhang (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Protective effects of parecoxib on rat primary astrocytes from oxidative stress induced by hydrogen peroxide - Yun-zhi Ling; Xiao-hong Li; Li Yu; Ye Zhang; Qi-sheng Liang; Xiao-di Yang; Hong-tao Wang (Journal of Zhejiang University-SCIENCE B, 2016)

Inhibition of five natural products from Chinese herbs on the growth of Chattonella marina - Fei Liu; Zheng-Bing He; Hong-Ye Li; Jie-Sheng Liu; Wei-Dong Yang (Environmental Science and Pollution Research, 2016)

Spherical cap harmonic analysis of regional magnetic anomalies based on CHAMP satellite data - Yan Feng; Yong Jiang; Yi Jiang; Bao-Jia Liu; Jin Jiang; Zhong-Wei Liu; Mei-Chen Ye; Hong-Shen Wang; Xiu-Ming Li (Applied Geophysics, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

The IL-1β/AP-1/miR-30a/ADAMTS-5 axis regulates cartilage matrix degradation in human osteoarthritis - Quanbo Ji; Xiaojie Xu; Qiang Zhang; Lei Kang; Yameng Xu; Ke Zhang; Ling Li; Yingchun Liang; Tian Hong; Qinong Ye; Yan Wang (Journal of Molecular Medicine, 2016)

miR-105/Runx2 axis mediates FGF2-induced ADAMTS expression in osteoarthritis cartilage - Quanbo Ji; Xiaojie Xu; Yameng Xu; Zhongyi Fan; Lei Kang; Ling Li; Yingchun Liang; Jing Guo; Tian Hong; Zhongli Li; Qiang Zhang; Qinong Ye; et al. (Journal of Molecular Medicine, 2016)

MRP functional activity and character in the dinoflagellate Prorocentrum lima - Dao-yi Hou; Jin-jin Liang; Cheng Zou; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Phase 1 clinical trial demonstrated that MUC1 positive metastatic seminal vesicle cancer can be effectively eradicated by modified Anti-MUC1 chimeric antigen receptor transduced T cells - Fengtao You; Licui Jiang; Bozhen Zhang; Qiang Lu; Qiao Zhou; Xiaoyang Liao; Hong Wu; Kaiqi Du; Youcai Zhu; Huimin Meng; Zhishu Gong; Yunhui Zong; et al. (Science China Life Sciences, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Procalcitonin Is a Stronger Predictor of Long-Term Functional Outcome and Mortality than High-Sensitivity C-Reactive Protein in Patients with Ischemic Stroke - Chao Wang; Li Gao; Zhi-Guo Zhang; Yu-Qian Li; Yan-Long Yang; Tao Chang; Long-Long Zheng; Xing-Ye Zhang; Ming-Hao Man; Li-Hong Li (Molecular Neurobiology, 2016)

Removal of Two Species of Harmful Algae Using Gramine Modified Montmorillonite - Su-li Liu; Wen-wen Wang; Fei Liu; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Bulletin of Environmental Contamination and Toxicology, 2016)

Isolation and characterization of the marine algicidal bacterium Pseudoalteromonas S1 against the harmful alga Akashiwo sanguinea - Hong-Ye Sun; Yu Zhang; Hui-Rong Chen; Chang-Xing Hu; Hui Li; Zhang-Li Hu (Marine Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Regional magnetic anomaly fields: 3D Taylor polynomial and surface spline models - Yan Feng; Yong Jiang; Yi Jiang; Zheng Li; Jin Jiang; Zhong-Wei Liu; Mei-Chen Ye; Hong-Sheng Wang; Xiu-Ming Li (Applied Geophysics, 2016)

Spatial analysis of gastric cancer morbidity in regions of rapid urbanization: a case study in Xiamen, China - JiLai Liu; XinHu Li; Tao Lin; Long Dai; GuoQin Zhang; ChaoSheng Zhang; Hong Ye; Vee Gibson; QianJun Zhao (Stochastic Environmental Research and Risk Assessment, 2016)

Complete genome sequence of a distinct calla lily chlorotic spot virus isolated in mainland China - Ye Xu; Si-bo Wang; Yong-zhong Li; Hong-zheng Tao; Ya-ning Huang; Bao-wei Wu; Yu-mei Dong; John Hu; Ya-ting Liu (Archives of Virology, 2016)

Experimental removal of Alexandrium tamarense cells using sulfobetaines and their modified clays - Jin-Jin Liang; Yun-Hui Li; Fei Liu; Hong-Ye Li; Jie-Sheng Liu; Wei-Dong Yang (Journal of Applied Phycology, 2015)

Unexpected decrease in yield and antioxidants in vegetable at very high CO2 levels - Yuming Fu; Lingzhi Shao; Hui Liu; Hongyan Li; Zhiruo Zhao; Peiliang Ye; Pingzhen Chen; Hong Liu (Environmental Chemistry Letters, 2015)

miR21 is Associated with the Cognitive Improvement Following Voluntary Running Wheel Exercise in TBI Mice - Tao Hu; Feng-Jie Zhou; Ye-Fei Chang; Ya-Shan Li; Guang-Cai Liu; Ying Hong; Hong-Lan Chen; Yan-Bin Xiyang; Tian-hao Bao (Journal of Molecular Neuroscience, 2015)

Lipoxin A4 Activates Nrf2 Pathway and Ameliorates Cell Damage in Cultured Cortical Astrocytes Exposed to Oxygen-Glucose Deprivation/Reperfusion Insults - Le Wu; Hong-Hua Li; Qiang Wu; Sen Miao; Zi-Jian Liu; Ping Wu; Du-Yun Ye (Journal of Molecular Neuroscience, 2015)

Identification, characterization and functional analysis of anti-apoptotic protein BCL-2-like gene from pufferfish, Takifugu obscurus, responding to bacterial challenge - Chang-Hong Cheng; Fang-Fang Yang; Shao-An Liao; Yu-Tao Miao; Chao-Xia Ye; An-Li Wang; Jin-Chang Liu; Li-Wei Liu (Fish Physiology and Biochemistry, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

A fast-convergence POCS seismic denoising and reconstruction method - Zi-Jian Ge; Jing-Ye Li; Shu-Lin Pan; Xiao-Hong Chen (Applied Geophysics, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Effect of acute ammonia exposure on expression of GH/IGF axis genes GHR1, GHR2 and IGF-1 in pufferfish (Takifugu obscurus) - Chang-Hong Cheng; Fang-Fang Yang; Shao-An Liao; Yu-Tao Miao; Chao-Xia Ye; An-Li Wang (Fish Physiology and Biochemistry, 2015)

Relationship of Blood Levels of Pb with Cu, Zn, Ca, Mg, Fe, and Hb in Children Aged 0∼6 Years from Wuhan, China - Jingping Ye; Chuang Du; Lu Wang; Zhen Li; Shaoxin Huang; Hong Wang; Liping He; Yongyi Bi; Chunhong Wang (Biological Trace Element Research, 2015)

Prognostic Value of Mannose-Binding Lectin: 90-Day Outcome in Patients with Acute Ischemic Stroke - Zhi-Guo Zhang; Chao Wang; Jing Wang; Zhuo Zhang; Yan-Long Yang; Li Gao; Xing-Ye Zhang; Tao Chang; Guo-Dong Gao; Li-Hong Li (Molecular Neurobiology, 2015)

Streptomyces ferrugineus sp. nov., isolated from mangrove soil in Thailand - Chang-ying Ruan; Li Zhang; Wan-wan Ye; Xiu-chao Xie; Rattanaporn Srivibool; Kannika Duangmal; Wasu Pathom-aree; Zi-xin Deng; Kui Hong (Antonie van Leeuwenhoek, 2015)

Isolation and characterization of dengue virus serotype 2 from the large dengue outbreak in Guangdong, China in 2014 - Hui Zhao; LingZhai Zhao; Tao Jiang; XiaoFeng Li; Hang Fan; WenXin Hong; Yu Zhang; Qin Zhu; Qing Ye; YiGang Tong; WuChun Cao; FuChun Zhang; et al. (Science China Life Sciences, 2014)

Intake of fruit and vegetables and risk of bladder cancer: a dose–response meta-analysis of observational studies - Baodong Yao; Yujie Yan; Xianwu Ye; Hong Fang; Huilin Xu; Yinan Liu; Sheran Li; Yanping Zhao (Cancer Causes & Control, 2014)

A new Alternaria species from grapevine in China - Wen-Chen Tao; Wei Zhang; Ji-Ye Yan; Kevin D. Hyde; Eric H. C. McKenzie; Xing-Hong Li; Yong Wang (Mycological Progress, 2014)

Construction of Novel Chloroplast Expression Vector and Development of an Efficient Transformation System for the Diatom Phaeodactylum tricornutum - Wei-Hong Xie; Cong-Cong Zhu; Nai-Sheng Zhang; Da-Wei Li; Wei-Dong Yang; Jie-Sheng Liu; Ramalingam Sathishkumar; Hong-Ye Li (Marine Biotechnology, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

Temporal changes in climatic variables and their impact on crop yields in southwestern China - Hong-Bin Liu; Yu Gou; Hong-Ye Wang; Hong-Mei Li; Wei Wu (International Journal of Biometeorology, 2014)

An innovative approach for iodine supplementation using iodine-rich phytogenic food - Huan-Xin Weng; Hui-Ping Liu; De-Wang Li; Mingli Ye; Lehua Pan; Tian-Hong Xia (Environmental Geochemistry and Health, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer - De-Bing Shi; Xin-Xiang Li; Hong-Tu Zheng; Da-Wei Li; Guo-Xiang Cai; Jun-Jie Peng; Wei-Lie Gu; Zu-Qing Guan; Ye Xu; San-Jun Cai (Cell Biochemistry and Biophysics, 2014)

Notch inhibition promotes fetal liver stem/progenitor cells differentiation into hepatocytes via the inhibition of HNF-1β - Tao Wang; Tao Chen; Hong-yin Liang; Hong-tao Yan; Ning Lin; Li-ye Liu; Hao Luo; Zhu Huang; Nan-lin Li; Wei-hui Liu; Li-jun Tang (Cell and Tissue Research, 2014)

Solid-phase extraction for selective determination of bisphenol A in drinks and fruits by dummy surface molecularly imprinted polymer with direct synthetic method - Jin Li; Hong Zhou; Yu-Xin Liu; Xiang-Yang Yan; Ye-Ping Xu; Shao-Min Liu (Food Additives & Contaminants: Part A, 2014)

Analysis of synonymous codon usage in enterovirus 71 - Hua Zhang; Hong-wei Cao; Feng-qi Li; Zi-ye Pan; Zhi-jun Wu; Yan-hong Wang; Yu-dong Cui (VirusDisease, 2014)

HER-2 overexpression and survival in colorectal cancer: a meta-analysis - Chao Li; Da-ren Liu; Long-yun Ye; Ling-na Huang; Sanjay Jaiswal; Xiao-wen Li; Hou-hong Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)

Systems‐level analysis of the metabolic responses of the diatom P haeodactylum tricornutum to phosphorus stress - Zhi‐Kai Yang; Jian‐Wei Zheng; Ying‐Fang Niu; Wei‐Dong Yang; Jie‐Sheng Liu; Hong‐Ye Li (Environmental Microbiology, 2014)
Summary Phosphorus is an important macronutrient. To understand the molecular and cellular responses to phosphorus stress better, transcriptome profiling in combination with biochemical investigations was conducted in the model diatom P haeodactylum tricornutum . Out of 10 402 predicted genes, 2491 and 405 genes were significantly upregulated or downregulated respectively. Unsurprisingly, genes associated with phosphate uptake were upregulated, such as the phosphate transporters and alkaline phosphatases. Genes encoding stress‐shock proteins were accordingly upregulated, including genes associated with stress‐responsive proteins, signal transduction and secondary metabolism. Additionally, genes related to protein translation, carbon fixation, glycolysis and the citric acid cycle were also upregulated. Genes associated with gene transcription were downregulated, thereby resulting in the upregulation of translation to compensate for the limited supply of messenger RNA . The downregulation of genes related to β ‐oxidation could contribute to the accumulation of fatty acids. Accordingly, triacylglycerols, which are important for energy storage, were determined to increase by 1.65‐fold. Intracellular membranes, other than chloroplast membranes, tended to be dispersed; this finding was in accordance with the increased transcription of a total of 11 genes encoding putative phospholipases. Taken together, this work revealed the coordination of multiple metabolic pathways and certain key genes in the adaptation of P . tricornutum to phosphorus stress.

Improvement of a gene targeting system for genetic manipulation in Penicillium digitatum - Qian Xu; Cong-yi Zhu; Ming-shang Wang; Xue-peng Sun; Hong-ye Li (Journal of Zhejiang University-SCIENCE B, 2014)

Proteomics to reveal metabolic network shifts towards lipid accumulation following nitrogen deprivation in the diatom Phaeodactylum tricornutum - Zhi-Kai Yang; Yu-Han Ma; Jian-Wei Zheng; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Journal of Applied Phycology, 2014)

Artificial antigen synthesis and the development of polyclonal antibody-based immunoassay for citreoviridin determination - Zhen Hong Zhuang; Shan Jin Que; Yue Ming Gao; Jun Yuan; Zhou Ye; Min Du; Guang Mei Lin; Li Cai Liu; Shi Hua Wang (World Journal of Microbiology and Biotechnology, 2014)

Male Accessory Gland Secretions Modulate Female Post-Mating Behavior in the Moth Spodoptera litura - Jin-Feng Yu; Cong Li; Jin Xu; Jian-Hong Liu; Hui Ye (Journal of Insect Behavior, 2014)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Antiarrhythmic effects and ionic mechanisms of allicin on myocardial injury of diabetic rats induced by streptozotocin - Wei Huang; Ye Wang; Yong-Gang Cao; Han-Ping Qi; Lei Li; Bing Bai; Yang Liu; Hong-Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Two type III polyketide synthases from Polygonum cuspidatum: gene structure, evolutionary route and metabolites - Yan-Wu Guo; Hui-Li Guo; Xing Li; Li-Li Huang; Bo-Ning Zhang; Xiao-Bin Pang; Ben-Ye Liu; Lan-Qing Ma; Hong Wang (Plant Biotechnology Reports, 2013)

Determination and Study on Residue and Dissipation of Florasulam in Wheat and Soil Under Field Conditions - Zhuonan Li; Wenbi Guan; Huijie Hong; Yong Ye; Yongqiang Ma (Bulletin of Environmental Contamination and Toxicology, 2013)

A rock-physical modeling method for carbonate reservoirs at seismic scale - Jing-Ye Li; Xiao-Hong Chen (Applied Geophysics, 2013)

Interactive effects of morphine and dopaminergic compounds on spatial working memory in rhesus monkeys - Jian-Hong Wang; Joshua Dominie Rizak; Yan-Mei Chen; Liang Li; Xin-Tian Hu; Yuan-Ye Ma (Neuroscience Bulletin, 2013)

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Synthesis, structure, and biological assay of cinnamic amides as potential EGFR kinase inhibitors - Mao Zhang; Xiang Lu; Hong-Jia Zhang; Na Li; Yu Xiao; Hai-Liang Zhu; Yong-Hao Ye (Medicinal Chemistry Research, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Note added in proof to: Molecular characterization of the pentacyclic triterpenoid biosynthetic pathway in Catharanthus roseus - Lili Huang; Jia Li; Hechun Ye; Changfu Li; Hong Wang; Benye Liu; Yansheng Zhang (Planta, 2012)

Molecular characterization of the pentacyclic triterpenoid biosynthetic pathway in Catharanthus roseus - Lili Huang; Jia Li; Hechun Ye; Changfu Li; Hong Wang; Benye Liu; Yansheng Zhang (Planta, 2012)

Phytoextraction of Cd-Contaminated Soils: Current Status and Future Challenges - Jin-Tian Li; Alan J. M. Baker; Zhi-Hong Ye; Hong-Bin Wang; Wen-Sheng Shu (Critical Reviews in Environmental Science and Technology, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

Identification of a pou2 ortholog in Chinese sturgeon, Acipenser sinensis and its expression patterns in tissues, immature individuals and during embryogenesis - Huan Ye; Hao Du; Xi-Hua Chen; Hong Cao; Tao Liu; Chuang-Ju Li (Fish Physiology and Biochemistry, 2012)

Improvement of myocardial glycolipid metabolic disorder in diabetic hamster with Astragalus polysaccharides treatment - Wei Chen; Yan-Ping Xia; Wen-Jie Chen; Mao-Hua Yu; Yi-Ming Li; Hong-Ying Ye (Molecular Biology Reports, 2012)

GWAS-linked GAK locus in Parkinson’s disease in Han Chinese and meta-analysis - Nan-Nan Li; Xue-Li Chang; Xue-Ye Mao; Jin-Hong Zhang; Dong-Mei Zhao; Eng-King Tan; Rong Peng (Human Genetics, 2012)

Synthesis and Bioactive Studies of Complex 8-Hydroxyquinolinato-Bis-(Salicylato) Yttrium (III) - Xu Li; Qiang-Guo Li; Hui Zhang; Ji-Lin Hu; Fei-Hong Yao; De-Jun Yang; Sheng-Xiong Xiao; Li-Juan Ye; Yi Huang; Dong-Cai Guo (Biological Trace Element Research, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Endogenous hydrogen peroxide is a key factor in the yeast extract-induced activation of biphenyl biosynthesis in cell cultures of Sorbus aucuparia - Xiaofang Qiu; Caiyan Lei; Lili Huang; Xing Li; He Hao; Zhigao Du; Hong Wang; Hechun Ye; Ludger Beerhues; Benye Liu (Planta, 2012)

Different sperm sources and parameters can influence intracytoplasmic sperm injection outcomes before embryo implantation - Yue-hong Lu; Hui-juan Gao; Bai-jia Li; Ying-ming Zheng; Ying-hui Ye; Yu-li Qian; Chen-ming Xu; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2012)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

The Mechanism of the Molecular Interaction between Cerium (III) and Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) - Chao Liu; Fa-shui Hong; Ye Tao; Tao Liu; Ya-ning Xie; Jian-hua Xu; Zhong-rui Li (Biological Trace Element Research, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Association of BLK (rs13277113, rs2248932) polymorphism with systemic lupus erythematosus: a meta-analysis - Ye Fan; Jin-Hui Tao; Li-Ping Zhang; Lian-Hong Li; Dong-Qing Ye (Molecular Biology Reports, 2011)

Multi-wave amplitude-preserved AVO modeling considering wave propagation effects - Bo Hou; Xiao-Hong Chen; Jing-Ye Li; Xiao-Zhen Zhang (Applied Geophysics, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Aucubin modulates Bcl-2 family proteins expression and inhibits caspases cascade in H2O2-induced PC12 cells - Hong Yu Xue; Dong Yan Niu; Gui Zhen Gao; Qiu Ye Lin; Li Ji Jin; Yong Ping Xu (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Metabolic engineering of artemisinin biosynthesis in Artemisia annua L. - Benye Liu; Hong Wang; Zhigao Du; Guofeng Li; Hechun Ye (Plant Cell Reports, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Seismic noise attenuation using nonstationary polynomial fitting - Guo-Chang Liu; Xiao-Hong Chen; Jing-Ye Li; Jing Du; Jia-Wen Song (Applied Geophysics, 2011)

Relationship between HPLC fingerprints and in vivo pharmacological effects of a traditional Chinese medicine: Radix Angelicae Dahuricae - Hong Nie; Hui Zhang; Xiao-qi Zhang; Yong Luo; Lan-zhen Meng; Zhen Yin; Jianyu Zhang; Kongyan Li; Ai-hua Xiong; Ling Zhong; Heqing Huang; Wen-cai Ye (Natural Product Research, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

The effect of the expression of angiotensin II on extracellular matrix metalloproteinase inducer (EMMPRIN) in macrophages is mediated via the AT1/COX-2/PGE2 pathway - Li-xia Yang; Jin-shan Ye; Rui-wei Guo; Hong Liu; Xian-mei Wang; Feng Qi; Chuanming Guo (Inflammation Research, 2010)

Irregular seismic data reconstruction based on exponential threshold model of POCS method - Jian-Jun Gao; Xiao-Hong Chen; Jing-Ye Li; Guo-Chang Liu; Jian Ma (Applied Geophysics, 2010)

Micropropagation of Pinus massoniana and mycorrhiza formation in vitro - Li-Hua Zhu; Xiao-Qin Wu; Hong-Ye Qu; Jing Ji; Jian-ren Ye (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Ectopic Expression of the Tomato Mi-1 Gene Confers Resistance to Root Knot Nematodes in Lettuce (Lactuca sativa) - Li-Ying Zhang; Yu-Yang Zhang; Ru-Gang Chen; Jun-Hong Zhang; Tao-Tao Wang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Structural basis for the action of xyloglucan endotransglycosylases/hydrolases: Insights from homology modeling - Qin Xu; Xia Ye; Li-Yan Li; Zong-Ming Cheng; Hong Guo (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Frequent occurrence of unreduced gametes in Triticum turgidum–Aegilops tauschii hybrids - Lian-Quan Zhang; Deng-Cai Liu; You-Liang Zheng; Ze-Hong Yan; Shou-Fen Dai; Yun-Fang Li; Qi Jiang; Ya-Qing Ye; Yang Yen (Euphytica, 2010)

Identification and characterization of a novel capsid protein encoded by Singapore grouper iridovirus ORF038L - Qing Jiao Wan; Jie Gong; Xiao Hong Huang; You Hua Huang; Sheng Zhou; Zheng Liang Ou-Yang; Jian Hao Cao; Li Li Ye; Qi Wei Qin (Archives of Virology, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Fas expression on peripheral blood lymphocytes in systemic lupus erythematosus: relation to the organ damage and lymphocytes apoptosis - Lian-Hong Li; Wen-Xian Li; Ou Wu; Guo-Qing Zhang; Hai-Feng Pan; Xiang-Pei Li; Jian-Hua Xu; Hong Dai; Dong-Qing Ye (Molecular Biology Reports, 2009)

Inhibition of the Growth of Alexandrium tamarense by Algicidal Substances in Chinese Fir (Cunninghamia lanceolata) - Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li; Xin-Lian Zhang; Yu-Zao Qi (Bulletin of Environmental Contamination and Toxicology, 2009)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Isolation and characterization of ten polymorphic microsatellite in the endangered tree Erythrophleum fordii oliv - Peng Zhu; Wan-Hui Ye; Zheng-Feng Wang; Hong-Lin Cao; Min Zhang; Ling Li; Wei Xiao (Conservation Genetics, 2009)

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L. - Gao-Bin Pu; Dong-Ming Ma; Jian-Lin Chen; Lan-Qing Ma; Hong Wang; Guo-Feng Li; He-Chun Ye; Ben-Ye Liu (Plant Cell Reports, 2009)

Multi-core structure of the Kuroshio in the East China Sea from long-term transect observations - Hong-Xia Chen; Fang-Li Qiao; Tal Ezer; Ye-Li Yuan; Feng Hua (Ocean Dynamics, 2009)

OsMT1a, a type 1 metallothionein, plays the pivotal role in zinc homeostasis and drought tolerance in rice - Zhao Yang; Yaorong Wu; Ye Li; Hong-Qing Ling; Chengcai Chu (Plant Molecular Biology, 2009)

Meta analysis on the association between FcγRIIa-R/H131 polymorphisms and systemic lupus erythematosus - Hui Yuan; Hai-Feng Pan; Lian-Hong Li; Jin-Bao Feng; Wen-Xian Li; Xiang-Pei Li; Dong-Qing Ye (Molecular Biology Reports, 2009)

Osteogenic differentiation of mesenchymal stem cells promoted by overexpression of connective tissue growth factor - Jin-jing Wang; Feng Ye; Li-jia Cheng; Yu-jun Shi; Ji Bao; Huai-qiang Sun; Wei Wang; Peng Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2009)

Identification of a Polygonum cuspidatum three-intron gene encoding a type III polyketide synthase producing both naringenin and p-hydroxybenzalacetone - Lan-Qing Ma; Yan-Wu Guo; Dong-Yao Gao; Dong-Ming Ma; You-Nian Wang; Guo-Feng Li; Ben-Ye Liu; Hong Wang; He-Chun Ye (Planta, 2009)

Expressions of cardiac sympathetic norepinephrine transporter and β1-adrenergic receptor decreased in aged rats - He Li; Xiao-qing Ma; Fan Ye; Jing Zhang; Xin Zhou; Zhi-hong Wang; Yu-ming Li; Guo-yuan Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

A novel type III polyketide synthase encoded by a three-intron gene from Polygonum cuspidatum - Lan-Qing Ma; Xiao-Bin Pang; Hai-Yan Shen; Gao-Bin Pu; Hua-Hong Wang; Cai-Yan Lei; Hong Wang; Guo-Feng Li; Ben-Ye Liu; He-Chun Ye (Planta, 2009)

Arabidopsis acyl-CoA-binding proteins ACBP4 and ACBP5 are subcellularly localized to the cytosol and ACBP4 depletion affects membrane lipid composition - Shi Xiao; Hong-Ye Li; Jiao-Ping Zhang; Suk-Wah Chan; Mee-Len Chye (Plant Molecular Biology, 2008)

Characterization of a putative pollen-specific arabinogalactan protein gene, BcMF8, from Brassica campestris ssp. chinensis - Li Huang; Jia-Shu Cao; Ai-Hong Zhang; Yi-Qun Ye (Molecular Biology Reports, 2008)

Application of principal component-radial basis function neural networks (PC-RBFNN) for the detection of water-adulterated bayberry juice by near-infrared spectroscopy - Li-juan Xie; Xing-qian Ye; Dong-hong Liu; Yi-bin Ying (Journal of Zhejiang University-SCIENCE B, 2008)

Use of starter culture of Lactobacillus plantarum BP04 in the preservation of dining-hall food waste - Zhi-Long Ye; Yan Zheng; Ya-Hong Li; Wei-Min Cai (World Journal of Microbiology and Biotechnology, 2008)

Agrobacterium tumefaciens-mediated genetic transformation of the phytopathogenic fungus Penicillium digitatum - Ji-ye Wang; Hong-ye Li (Journal of Zhejiang University-SCIENCE B, 2008)

Identification and characterization of EST-SSRs and cpSSRs in endangered Cycas hainanensis - Zheng-Feng Wang; Wan-Hui Ye; Hong-Lin Cao; Zhong-Chao Li; Shao-Lin Peng (Conservation Genetics, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Activities and Toxicity of a Novel Plant Growth Regulator 2-Furan-2-yl-[1,3] Dioxolane - Tian Rui Ren; Yan Hong Xie; Wei Wen Zhu; Yong Hong Li; Ye Zhang (Journal of Plant Growth Regulation, 2007)

A unique highly thermostable 2-phosphoglycerate forming glycerate kinase from the hyperthermophilic archaeon Pyrococcus horikoshii: gene cloning, expression and characterization - Bo Liu; Ye Hong; Lei Wu; Zhuo Li; Jinfeng Ni; Duohong Sheng; Yulong Shen (Extremophiles, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular cloning and overexpression of a novel UDP-glucosyltransferase elevating salidroside levels in Rhodiola sachalinensis - Lan-Qing Ma; Ben-Ye Liu; Dong-Yao Gao; Xiao-Bin Pang; Shi-You Lü; Han-Song Yu; Hong Wang; Fang Yan; Zhen-Qiu Li; Yan-Fang Li; He-Chun Ye (Plant Cell Reports, 2007)

Cloning, expression and characterization of a thermostable exo-β-D-glucosaminidase from the hyperthermophilic archaeon Pyrococcus horikoshii - Bo Liu; Zhuo Li; Ye Hong; Jinfeng Ni; Duohong Sheng; Yulong Shen (Biotechnology Letters, 2006)

Arabidopsis ACBP3 is an extracellularly targeted acyl-CoA-binding protein - Ka-Chun Leung; Hong-Ye Li; Shi Xiao; Muk-Hei Tse; Mee-Len Chye (Planta, 2006)

Pharmacokinetic study with N-Ile1-Thr2-63-desulfato-r-hirudin in rabbits by means of bioassay - Guo-zhu Han; Hong-can Ren; Yong Lu; Ying Li; Shu Xiao; Hong-wei Ye; He-mu Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)

ACBP4 and ACBP5, novel Arabidopsis acyl-CoA-binding proteins with kelch motifs that bind oleoyl-CoA - Ka-Chun Leung; Hong-Ye Li; Girish Mishra; Mee-Len Chye (Plant Molecular Biology, 2005)

SYNTHESIS BIODISTRIBUTION AND QSAR STUDIES OF FIVE Tc-99M LABELED NOVEL N3S PSEUDO-PEPTIDE COMPLEXES - Hua-bei Zhang; Hai-hong Ye; Ya-ling Zhang; Xuefang Zheng; Jian-sheng Han; Hua Li; Chun-ping Liu (Medicinal Chemistry Research, 2005)

Spatial and Temporal Variations of Sound Speed at the PN Section - Lian-Gang Lü; Hong-Xia Chen; Ye-Li Yuan (Journal of Oceanography, 2004)

ACBP4 and ACBP5, novel Arabidopsis acyl-CoA-binding proteins with kelch motifs that bind oleoyl-CoA - Ka-Chun Leung; Hong-Ye Li; Girish Mishra; Mee-Len Chye (Plant Molecular Biology, 2004)

Arabidopsis Acyl-CoA-Binding Protein ACBP2 Interacts With an Ethylene-Responsive Element-Binding Protein, AtEBP, via its Ankyrin Repeats - Hong-Ye Li; Mee-Len Chye (Plant Molecular Biology, 2004)

Membrane localization of Arabidopsis acyl-CoA binding protein ACBP2 - Hong-Ye Li; Mee-Len Chye (Plant Molecular Biology, 2003)

G-box binding coincides with increased Solanum melongena cysteine proteinase expression in senescent fruits and circadian-regulated leaves - Zeng-Fu Xu; Mee-Len Chye; Hong-Ye Li; Fang-Xiu Xu; Kwok-Ming Yao (Plant Molecular Biology, 2003)

Delayed cardioprotection induced by nitroglycerin is mediated by alpha-calcitonin gene-related peptide - Zhi-Hong Zhou; Jun Peng; Feng Ye; Nian-Sheng Li; Han-Wu Deng; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

The design of new molecular "light switches" for DNA - Xiao-Hua Zou; Bao-Hui Ye; Hong Li; Qian-Ling Zhang; Hui Chao; Jin-Gang Liu; Liang-Nian Ji; Xiao-Yuan Li (JBIC Journal of Biological Inorganic Chemistry, 2001)

Single amino acid substitutions at the acyl-CoA-binding domain interrupt 14[C]palmitoyl-CoA binding of ACBP2, an Arabidopsis acyl-CoA-binding protein with ankyrin repeats - Mee-Len Chye; Hong-Ye Li; Mei-Hing Yung (Plant Molecular Biology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Myosin light chain kinase from skeletal muscle regulates an ATP-dependent interaction between actin and myosin by binding to actin - Koichiro Fujita; Koichiro Fujita; Li-Hong Ye; Manabu Sato; Tsuyoshi Okagaki; Yukio Nagamachi; Kazuhiro Kohama (Molecular and Cellular Biochemistry, 1999)